Composition for functional layer of electrochemical element, laminate for electrochemical element, and electrochemical element
By using a granular polymer with different volume average particle sizes and a composition containing reactive monomer units, the problem of insufficient adhesion of the functional layer of the electrochemical element is solved, and high adhesion, heat resistance and excellent electrochemical properties are achieved.
Patent Information
- Application Number
- CN202380059193.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-08-24
- Publication Date
- 2025-03-11
AI Technical Summary
There is room for improvement in the adhesion of the existing electrochemical element functional layers, especially in the adhesion before and after the electrolyte impregnation.
A composition comprising a particulate polymer (X) and a particulate polymer (Y) is used, wherein the volume average particle size of the particulate polymer (X) is greater than that of the particulate polymer (Y), and one of them contains reactive monomer unit A and the other contains reactive monomer unit B.
A functional layer with excellent adhesion is formed, which improves the adhesion strength and heat resistance between components, and enhances the breathability and ion conductivity of the functional layer.
Abstract
Description
Technical Field
[0001] The present invention relates to a composition for an electrochemical device functional layer, a laminate for an electrochemical device, and an electrochemical device. Background Art
[0002] Electrochemical devices such as lithium-ion secondary batteries and electric double layer capacitors are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and are therefore used in a wide range of applications.
[0003] Here, for example, a lithium ion secondary battery generally includes a positive electrode, a negative electrode, and battery components such as a separator that separates the positive electrode from the negative electrode to prevent a short circuit between the positive electrode and the negative electrode.
[0004] In electrochemical elements such as lithium-ion secondary batteries, components having functional layers such as heat-resistant layers for the purpose of improving the heat resistance of components and adhesive layers for the purpose of improving the adhesion between components are used. Specifically, an electrode formed by further forming a functional layer on an electrode substrate formed by arranging an electrode composite material layer on a current collector, and a separator formed by forming a functional layer on a separator substrate are used as battery components. Such a functional layer is formed by applying a composition for a secondary battery functional layer on a substrate such as a separator substrate and drying the coating on the substrate. Moreover, in recent years, further improvements in the functional layer are being studied for the purpose of further improving the performance of electrochemical elements such as lithium-ion secondary batteries. Specifically, in, for example, patent documents 1 to 3, a scheme of a functional layer comprising two granular polymers with different particle sizes is proposed. According to patent documents 1 to 3, it is reported that among the two granular polymers, the first granular polymer with a large particle size can function as adhesive particles for bonding constituent components to each other via a functional layer, and the second granular polymer with a small particle size can function as an adhesive material for bonding the first granular polymer and components such as non-conductive heat-resistant particles contained in the functional layer to each other to prevent them from falling off.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent document 1: International Publication No. 2020 / 175292;
[0008] Patent document 2: International Publication No. 2020 / 246394;
[0009] Patent document 3: International Publication No. 2021 / 085144. Summary of the invention
[0010] Problem that the invention aims to solve
[0011] However, the functional layer of the prior art still has room for improvement in terms of adhesion. In addition, the adhesion required for the functional layer includes, for example, adhesion before electrolyte immersion (hereinafter, sometimes referred to as "dry adhesion") and adhesion after electrolyte immersion (hereinafter, sometimes referred to as "wet adhesion"), etc.
[0012] Therefore, an object of the present invention is to provide a composition for an electrochemical element functional layer capable of forming a functional layer having excellent adhesiveness.
[0013] Another object of the present invention is to provide an electrochemical device laminate having a functional layer formed using the electrochemical device functional layer composition, and an electrochemical device having the electrochemical device laminate.
[0014] Solutions for solving problems
[0015] The present inventors have conducted intensive studies to achieve the above-mentioned object. Then, the present inventors have newly found that a functional layer having excellent adhesiveness can be formed by using a composition for a functional layer comprising a granular polymer (X) and a granular polymer (Y) having a volume average particle diameter smaller than the volume average particle diameter of the granular polymer (X), wherein one of the granular polymer (X) and the granular polymer (Y) contains a predetermined reactive monomer unit A and the other contains a predetermined reactive monomer unit B, thereby completing the present invention.
[0016] That is, the object of the present invention is to advantageously solve the above-mentioned problems. The present invention is [1] a composition for a functional layer of an electrochemical element, comprising a granular polymer (X) and a granular polymer (Y), wherein the volume average particle size of the granular polymer (Y) is smaller than the volume average particle size of the granular polymer (X), wherein one of the granular polymer (X) and the granular polymer (Y) contains a reactive monomer unit A and the other contains a reactive monomer unit B, wherein the reactive monomer unit A is an epoxy-containing monomer unit or a hydroxyl-containing monomer unit, and when the reactive monomer unit A is an epoxy-containing monomer unit, the reactive monomer unit B contains at least one selected from a (meth)acrylamide-containing monomer unit, an acid anhydride monomer unit, a sulfonic acid-containing monomer unit, a phosphoric acid-containing monomer unit and an amino-containing monomer unit, and when the reactive monomer unit A is a hydroxyl-containing monomer unit, the reactive monomer unit B contains at least one selected from a (meth)acrylamide-containing monomer unit, a carboxylic acid-containing monomer unit, an acid anhydride monomer unit, a sulfonic acid-containing monomer unit, a phosphoric acid-containing monomer unit and an epoxy-containing monomer unit.
[0017] If a functional layer composition is used that includes a granular polymer (X) and a granular polymer (Y) having a volume average particle size smaller than the volume average particle size of the granular polymer (X), and one of the granular polymer (X) and the granular polymer (Y) contains the above-specified reactive monomer unit A and the other contains the above-specified reactive monomer unit B, a functional layer with excellent adhesion can be formed.
[0018] In the present invention, unless otherwise specified, the phrase "containing a monomer unit" in a polymer means that "a polymer obtained by using the monomer contains a structural unit derived from the monomer".
[0019] Furthermore, in the present invention, "(meth)acrylamide" means acrylamide and / or methacrylamide.
[0020] In the present invention, with respect to the "epoxy-containing monomer unit" contained in the granular polymer of one of the granular polymer (X) and the granular polymer (Y), when the other granular polymer does not contain the hydroxyl-containing monomer unit as the reactive monomer unit A, it is treated as the "reactive monomer unit A", and when the other granular polymer contains the hydroxyl-containing monomer unit as the reactive monomer unit A, it is treated as the "reactive monomer unit B".
[0021] In the present invention, the volume average particle diameter of the particulate polymers (X) and (Y) can be measured using the method described in the examples of this specification. In addition, the fact that the composition for the functional layer contains the particulate polymer (X) and the particulate polymer (Y) having a volume average particle diameter smaller than the volume average particle diameter of the particulate polymer (X) can be determined by observing, for example, a peak corresponding to the particulate polymer (X) on the side with a larger particle diameter and a peak corresponding to the particulate polymer (Y) on the side with a smaller particle diameter in the particle diameter distribution (volume basis) measured by a laser diffraction method.
[0022] [2] In the composition for an electrochemical device functional layer according to [1] above, the volume average particle size of the particulate polymer (X) is preferably 1 μm or more and 10 μm or less.
[0023] When the volume average particle size of the particulate polymer (X) is within the above-specified range, the adhesiveness of the functional layer formed using the composition for a functional layer can be further improved, and the heat resistance of the functional layer can be improved.
[0024] [3] In the composition for electrochemical element functional layer of the above-mentioned [1] or [2], the above-mentioned granular polymer (X) preferably contains at least one selected from aromatic monovinyl monomer units, (meth)acrylate cycloalkyl ester monomer units and (meth)acrylate alkyl ester monomer units.
[0025] It should be noted that, in the present invention, "(meth)acrylic acid alkyl ester" does not include "(meth)acrylic acid cycloalkyl ester". That is, the "alkyl" of the (meth)acrylic acid alkyl ester means a chain (straight chain or branched) saturated hydrocarbon group, and the "cycloalkyl" which is a cyclic saturated hydrocarbon group of the (meth)acrylic acid cycloalkyl ester is not included in the "alkyl".
[0026] [4] In the composition for an electrochemical device functional layer according to any one of [1] to [3] above, the particulate polymer (Y) preferably contains at least one of an aromatic monovinyl monomer unit and an alkyl (meth)acrylate monomer unit.
[0027] [5] In the composition for an electrochemical device functional layer according to any one of [1] to [4] above, the content of the particulate polymer (Y) is preferably 10 parts by mass or more and 200 parts by mass or less relative to 100 parts by mass of the particulate polymer (X).
[0028] If the content of the granular polymer (Y) is within the range specified above, the adhesion of the functional layer formed using the functional layer composition can be further improved, and the gaps between the components in the functional layer can be fully ensured to improve the air permeability of the functional layer and the ion conductivity, thereby improving the output characteristics of the electrochemical element having the functional layer.
[0029] [6] The composition for an electrochemical device functional layer according to any one of [1] to [5] above preferably further contains non-conductive heat-resistant particles.
[0030] If the composition for a functional layer further contains non-conductive heat-resistant particles, the heat resistance of the functional layer can be improved using the composition for a functional layer.
[0031] [7] In the electrochemical device functional layer composition of [6] above, the content of the particulate polymer (Y) is preferably 0.5 parts by mass or more and 6 parts by mass or less per 100 parts by mass of the non-conductive heat-resistant particles.
[0032] If the content of the granular polymer (Y) is within the range specified above, the adhesion of the functional layer formed using the functional layer composition can be further improved, and the gaps between the components in the functional layer can be fully ensured to improve the air permeability of the functional layer and the ion conductivity, thereby improving the output characteristics of the electrochemical element having the functional layer.
[0033] In addition, the purpose of the present invention is to advantageously solve the above-mentioned problems. The present invention is [8] a laminate for an electrochemical element, which has a substrate and a functional layer for an electrochemical element formed on the above-mentioned substrate, and the above-mentioned functional layer for an electrochemical element is formed using the composition for the functional layer of an electrochemical element of any one of the above-mentioned [1] to [7].
[0034] Such an electrochemical device laminate can improve the electrochemical characteristics (for example, cycle characteristics, output characteristics, etc.) of an electrochemical device having the electrochemical device laminate.
[0035] [9] In the electrochemical device laminate of [8] above, the ratio of the volume average particle size of the granular polymer (X) to the thickness of the non-conductive heat-resistant particle layer formed of the non-conductive heat-resistant particles is preferably 0.8 or more and 10 or less.
[0036] In the present invention, the thickness of the non-conductive heat-resistant particle layer can be measured using the method described in Examples of the present specification.
[0037] Furthermore, an object of the present invention is to advantageously solve the above-mentioned problems. The present invention is
[10] an electrochemical device comprising the electrochemical device laminate according to [8] or [9] above.
[0038] Such an electrochemical element can exhibit excellent electrochemical characteristics (for example, cycle characteristics and output characteristics).
[0039] Effects of the Invention
[0040] According to the present invention, a composition for an electrochemical element functional layer capable of forming a functional layer having excellent adhesiveness can be provided.
[0041] Furthermore, according to the present invention, it is possible to provide an electrochemical device laminate having a functional layer formed using the electrochemical device functional layer composition, and an electrochemical device having the electrochemical device laminate. DETAILED DESCRIPTION
[0042] Hereinafter, embodiments of the present invention will be described in detail.
[0043] Here, the electrochemical element functional layer composition of the present invention (hereinafter, also simply referred to as "functional layer composition") can be used as a material for forming a functional layer possessed by the electrochemical element laminate of the present invention (hereinafter, also simply referred to as "laminate"). In addition, the electrochemical element laminate of the present invention can be used to manufacture the electrochemical element of the present invention.
[0044] (Composition for electrochemical element functional layer)
[0045] The composition for the electrochemical element functional layer of the present invention comprises at least a granular polymer (X) and a granular polymer (Y). Here, the volume average particle size of the granular polymer (X) is larger than the volume average particle size of the granular polymer (Y). Moreover, one of the granular polymer (X) and the granular polymer (Y) contains a prescribed reactive monomer unit A, and the other contains a prescribed reactive monomer unit B. According to the composition for the functional layer of the present invention, a functional layer with excellent adhesion can be formed.
[0046] In addition, the composition for the functional layer of the present invention may optionally contain non-conductive heat-resistant particles, amine compounds and other components in addition to the above-mentioned granular polymer (X) and granular polymer (Y). In addition, the composition for the functional layer of the present invention may be a slurry composition in which the granular polymer (X) and the granular polymer (Y) are dispersed in a dispersion medium such as water.
[0047] In the functional layer formed using the composition for the functional layer of the present invention, the reactive monomer unit A present on the surface of one of the granular polymer (X) and the granular polymer (Y) reacts with the reactive monomer unit B present on the surface of the other of them to form a bond. Thus, the granular polymer (X) and the granular polymer (Y) are firmly bonded, and as a result, the bonding strength of the granular polymer (X) and the non-conductive heat-resistant particles via the granular polymer (Y) and the bonding strength of the granular polymer (X) to each other via the granular polymer (Y) can be improved. Thus, the granular polymer (X) that can function as an adhesive particle can be suppressed from detaching from the functional layer, so that the adhesion between the components via the functional layer (that is, the adhesion of the functional layer) can be fully improved.
[0048] <Reactive monomer unit>
[0049] In the composition for a functional layer of the present invention, one of the particulate polymer (X) and the particulate polymer (Y) contains the reactive monomer unit A, and the other contains the reactive monomer unit B.
[0050] Here, in the functional layer composition of the present invention, the particulate polymer (X) may contain at least one of the reactive monomer unit A and the reactive monomer unit B, and the particulate polymer (Y) may contain at least the other of the reactive monomer unit A and the reactive monomer unit B.
[0051] For example, in the composition for a functional layer of the present invention,
[0052] (1) A granular polymer (X) containing both reactive monomer units A and reactive monomer units B, and a granular polymer (Y) containing both reactive monomer units A and reactive monomer units B can be used.
[0053] (2) A granular polymer (X) containing both reactive monomer units A and reactive monomer units B, and a granular polymer (Y) containing reactive monomer units A but not reactive monomer units B may be used.
[0054] (3) A granular polymer (X) containing both reactive monomer units A and reactive monomer units B, and a granular polymer (Y) containing no reactive monomer units A and containing reactive monomer units B may be used.
[0055] (4) A granular polymer (X) containing reactive monomer units A but not reactive monomer units B, and a granular polymer (Y) containing both reactive monomer units A and reactive monomer units B may be used.
[0056] (5) A granular polymer (X) containing no reactive monomer unit A and containing reactive monomer unit B, and a granular polymer (Y) containing both reactive monomer unit A and reactive monomer unit B can be used.
[0057] (6) A granular polymer (X) containing reactive monomer units A but not containing reactive monomer units B, and a granular polymer (Y) containing reactive monomer units B but not containing reactive monomer units A can be used.
[0058] (7) A granular polymer (X) containing no reactive monomer unit A and containing reactive monomer unit B, and a granular polymer (Y) containing reactive monomer unit A and containing no reactive monomer unit B can be used.
[0059] Moreover, the reactive monomer unit A is easier to introduce into the granular polymer (X) than the reactive monomer unit B. Therefore, in the functional layer composition of the present invention, it is preferred to use (6) a granular polymer (X) containing the reactive monomer unit A but not containing the reactive monomer unit B, and a granular polymer (Y) containing the reactive monomer unit B but not containing the reactive monomer unit A.
[0060] <<Reactive monomer unit A>>
[0061] The reactive monomer unit A is an epoxy group-containing monomer unit or a hydroxyl group-containing monomer unit.
[0062] In addition, when the particulate polymer (X) contains an epoxy group-containing monomer unit as the reactive monomer unit A, the particulate polymer (X) is not particularly limited, and usually does not contain a hydroxyl group-containing monomer unit as the reactive monomer unit A. In addition, when the particulate polymer (X) contains a hydroxyl group-containing monomer unit as the reactive monomer unit A, the particulate polymer (X) is not particularly limited, and usually does not contain an epoxy group-containing monomer unit as the reactive monomer unit A.
[0063] Similarly, when the particulate polymer (Y) contains an epoxy group-containing monomer unit as the reactive monomer unit A, the particulate polymer (Y) is not particularly limited, and usually does not contain a hydroxyl group-containing monomer unit as the reactive monomer unit A. Furthermore, when the particulate polymer (Y) contains a hydroxyl group-containing monomer unit as the reactive monomer unit A, the particulate polymer (Y) is not particularly limited, and usually does not contain an epoxy group-containing monomer unit as the reactive monomer unit A.
[0064] [Epoxy-containing monomer units]
[0065] Examples of epoxy-containing monomers that can form epoxy-containing monomer units include unsaturated glycidyl ethers such as vinyl glycidyl ether, allyl glycidyl ether, butenyl glycidyl ether, o-allylphenyl glycidyl ether, and glycidyl (2-butenyl) ether; and monoepoxides of dienes or polyenes such as butadiene monoepoxide, chloroprene monoepoxide, 4,5-epoxy-2-pentene, 3,4-epoxy-1-vinylcyclohexene, and 1,2-epoxy-5,9-cyclododecadiene. ; Alkenyl epoxides such as 3,4-epoxy-1-butene, 1,2-epoxy-5-hexene, and 1,2-epoxy-9-decene; glycidyl esters of unsaturated carboxylic acids such as glycidyl acrylate, glycidyl methacrylate, glycidyl crotonate, glycidyl 4-heptenoate, glycidyl sorbate, glycidyl linoleate, glycidyl 4-methyl-3-pentenoate, glycidyl ester of 3-cyclohexenecarboxylic acid, and glycidyl ester of 4-methyl-3-cyclohexenecarboxylic acid.
[0066] In addition, these epoxy group-containing monomers may be used alone or in combination of two or more at any ratio.
[0067] Among them, from the viewpoint of further improving the adhesiveness (especially wet adhesiveness) of the functional layer formed using the functional layer composition, it is preferred to use unsaturated glycidyl ethers and glycidyl esters of unsaturated carboxylic acids as the epoxy group-containing monomer, more preferably allyl glycidyl ether and glycidyl methacrylate, and even more preferably glycidyl methacrylate.
[0068] [Hydroxy-containing monomer unit]
[0069] Examples of the hydroxyl-containing monomers that can form the hydroxyl-containing monomer units include 2-hydroxyethyl acrylate (2-hydroxyethyl acrylate), 2-hydroxypropyl acrylate, 4-hydroxybutyl acrylate (4-hydroxybutyl acrylate), 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl methacrylate, di-2-hydroxyethyl maleate, di-4-hydroxybutyl maleate, di-2-hydroxypropyl itaconate, 1,4-cyclohexanedimethanol monoacrylate, and alkanol esters of ethylenically unsaturated carboxylic acids such as 2-hydroxyethyl acrylate (2-hydroxyethyl acrylate), 2-hydroxypropyl acrylate, and 2-hydroxy-3-phenoxypropyl acrylate; general formula: CH2=CR 1 -COO-(C q H 2q O) p -H (wherein, p represents an integer of 2 to 9, q represents an integer of 2 to 4, R 1 Esters of polyalkylene glycol represented by methyl or hydrogen and (meth)acrylic acid; mono(meth)acrylates of dihydroxy esters of dicarboxylic acids such as 2-hydroxyethyl-2'-(meth)acryloyloxyphthalate and 2-hydroxyethyl-2'-(meth)acryloyloxysuccinate; vinyl ethers such as 2-hydroxyethyl vinyl ether and 2-hydroxypropyl vinyl ether; (meth)allyl-2-hydroxyethyl ether, (meth)allyl-2-hydroxypropyl ether, (meth)allyl-3-hydroxypropyl ether, (meth)allyl-2-hydroxybutyl ether, (meth)allyl-3-hydroxybutyl ether, (meth)allyl-4-hydroxybutyl ether, (meth)allyl-6-hydroxybutyl ether, (meth)allyl-6-hydroxybutyl ether, (meth)allyl-6-hydroxybutyl ether, (meth)allyl-6-hydroxybutyl ether, (meth)allyl-6-hydroxybutyl ether, (meth)allyl-6-hydroxybutyl ether, (meth)allyl-6-hydroxybutyl ether, (meth)allyl-6-hydroxybutyl ether, (meth)allyl-6-hydroxyethyl ether, (meth)allyl-2-hydroxyethyl ether, (meth)allyl-2-hydroxypropyl ether, (meth)allyl-3-hydroxypropyl ether, (meth)allyl-2 ... Mono(meth)allyl ethers of alkylene glycols such as -hydroxyhexyl ether; mono(meth)allyl ethers of polyoxyalkylene glycols such as diethylene glycol mono(meth)allyl ether and dipropylene glycol mono(meth)allyl ether; mono(meth)allyl ethers of halogen and hydroxyl-substituted (poly)alkylene glycols such as glycerol mono(meth)allyl ether, (meth)allyl-2-chloro-3-hydroxypropyl ether and (meth)allyl-2-hydroxy-3-chloropropyl ether; mono(meth)allyl ethers of polyphenols such as eugenol and isoeugenol and their halogen-substituted products; (meth)allyl sulfide ethers of alkylene glycols such as (meth)allyl-2-hydroxyethyl sulfide and (meth)allyl-2-hydroxypropyl sulfide, etc.
[0070] In addition, these hydroxyl group-containing monomers may be used alone or in combination of two or more at any ratio.
[0071] Among them, from the viewpoint of further improving the adhesion (especially wet adhesion) of the functional layer formed using the functional layer composition, as the hydroxyl-containing monomer, it is preferred to use an alkyl alcohol ester of an ethylenically unsaturated carboxylic acid, and it is more preferred to use 4-hydroxybutyl acrylate (4-hydroxybutyl acrylate), 1,4-cyclohexanedimethanol monoacrylate, and 2-hydroxy-3-phenoxypropyl acrylate.
[0072] In addition, (meth)acrylamide group-containing monomers having a hydroxyalkyl group such as N-methylol (meth)acrylamide described later are not included in the hydroxyl group-containing monomers.
[0073] Furthermore, in the present invention, "(meth)allyl group" means an allyl group and / or a methallyl group.
[0074] <<Reactive monomer unit B>>
[0075] The reactive monomer unit B is a monomer unit that can react with the reactive monomer unit A to form a bond. The type of the reactive monomer unit B is selected according to the type of the reactive monomer unit A.
[0076] [Reactive Monomer Unit B1]
[0077] Specifically, when the reactive monomer unit A is an epoxy-containing monomer unit, the reactive monomer unit B (hereinafter sometimes referred to as "reactive monomer unit B1") needs to contain at least one selected from a (meth)acrylamide-containing monomer unit, an acid anhydride monomer unit, a sulfonic acid group-containing monomer unit, a phosphoric acid group-containing monomer unit and an amino group-containing monomer unit.
[0078] In addition, the reactive monomer unit B1 may further contain a carboxylic acid group-containing monomer unit. For example, when the granular polymer (Y) contains the reactive monomer unit B1, if the granular polymer (Y) further contains a carboxylic acid group-containing monomer unit as the reactive monomer unit B1, the stability during the preparation of the granular polymer (Y) can be improved.
[0079] The reactive monomer unit B1 is not particularly limited, but generally does not contain monomer units other than the above-mentioned (meth)acrylamide group-containing monomer unit, acid anhydride monomer unit, sulfonic acid group-containing monomer unit, phosphoric acid group-containing monomer unit, amino group-containing monomer unit, and carboxylic acid group-containing monomer unit.
[0080] -(Meth)acrylamide-containing monomer units-
[0081] The (meth)acrylamide-containing monomer capable of forming the (meth)acrylamide-containing monomer unit has the general formula: CH2=CR 2 -COO-NH-R 3 (Where R 2is hydrogen or methyl, R 3 is a hydrogen atom or an arbitrary substituent). In the above formula, R 3 The group is not particularly limited, but is preferably a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or a hydroxyalkyl group having 1 to 10 carbon atoms, more preferably a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, or a hydroxyalkyl group having 1 to 5 carbon atoms, and still more preferably a hydrogen atom.
[0082] Examples of the (meth)acrylamide group-containing monomer capable of forming the (meth)acrylamide group-containing monomer unit include (meth)acrylamide, N-methyl(meth)acrylamide, N-isopropyl(meth)acrylamide, and N-methylol(meth)acrylamide.
[0083] These (meth)acrylamide group-containing monomers may be used alone or in combination of two or more at any ratio.
[0084] Among them, acrylamide is preferably used as the (meth)acrylamide group-containing monomer.
[0085] -Anhydride monomer unit-
[0086] Examples of the acid anhydride monomer capable of forming the acid anhydride monomer unit include anhydrides of dicarboxylic acids such as maleic anhydride, methylmaleic anhydride, and dimethylmaleic anhydride.
[0087] In addition, these acid anhydride monomers may be used alone or in combination of two or more at any ratio.
[0088] Among them, maleic anhydride is preferably used as the acid anhydride monomer.
[0089] -Sulfonic acid group-containing monomer unit-
[0090] Examples of the sulfonic acid group-containing monomer capable of forming the sulfonic acid group-containing monomer unit include vinyl sulfonic acid, methylvinylsulfonic acid, (meth)allylsulfonic acid, ethyl (meth)acrylate-2-sulfonate, 2-acrylamido-2-methylpropanesulfonic acid, and 3-allyloxy-2-hydroxypropanesulfonic acid.
[0091] These sulfonic acid group-containing monomers may be used alone or in combination of two or more at any ratio.
[0092] - Phosphoric acid group-containing monomer unit
[0093] Examples of the phosphoric acid group-containing monomer capable of forming the phosphoric acid group-containing monomer unit include 2-(meth)acryloyloxyethyl phosphate, methyl-2-(meth)acryloyloxyethyl phosphate, and ethyl-(meth)acryloyloxyethyl phosphate.
[0094] In the present invention, "(meth)acryloyl" means acryloyl and / or methacryloyl.
[0095] These phosphoric acid group-containing monomers may be used alone or in combination of two or more at any ratio.
[0096] -Amino-containing monomer units-
[0097] The amino group-containing monomer capable of forming the amino group-containing monomer unit is an amine compound, and is a monomer having a polymerizable reactive group. In addition, the amine compound capable of being used as the amino group-containing monomer is preferably a primary amine compound or a secondary amine compound.
[0098] Examples of the amino group-containing monomer include aminoethyl vinyl ether and the like.
[0099] The amino group-containing monomer may be used alone or in combination of two or more at any ratio.
[0100] In addition, the amino group-containing monomer unit can be introduced into the granular polymer by chemically modifying the granular polymer obtained by the polymerization reaction of the monomers. In addition, when an amino group is introduced into a monomer unit other than the amino group-containing monomer unit in the granular polymer by chemical modification, the monomer unit into which the amino group is introduced is treated as an amino group-containing monomer unit.
[0101] -Carboxylic acid group-containing monomer unit-
[0102] Examples of carboxylic acid group-containing monomers that can form carboxylic acid group-containing monomer units include monocarboxylic acids and dicarboxylic acids. Examples of monocarboxylic acids include acrylic acid, methacrylic acid, and crotonic acid. Examples of dicarboxylic acids include maleic acid, fumaric acid, and itaconic acid.
[0103] These carboxylic acid group-containing monomers may be used alone or in combination of two or more at any ratio.
[0104] Among them, as the carboxylic acid group-containing monomer, acrylic acid, methacrylic acid, and itaconic acid are preferably used, methacrylic acid and itaconic acid are more preferably used, and methacrylic acid is further preferably used.
[0105] [Reactive Monomer Unit B2]
[0106] In addition, when the reactive monomer unit A is a hydroxyl group-containing monomer unit, the reactive monomer unit B (hereinafter sometimes referred to as "reactive monomer unit B2") needs to contain at least one selected from a (meth)acrylamide group-containing monomer unit, a carboxylic acid group-containing monomer unit, an acid anhydride monomer unit, a sulfonic acid group-containing monomer unit, a phosphoric acid group-containing monomer unit and an epoxy group-containing monomer unit.
[0107] The reactive monomer unit B2 is not particularly limited, but generally does not contain monomer units other than the above-mentioned (meth)acrylamide group-containing monomer unit, carboxylic acid group-containing monomer unit, acid anhydride monomer unit, sulfonic acid group-containing monomer unit, phosphoric acid group-containing monomer unit, and epoxy group-containing monomer unit.
[0108] Specific examples and preferred examples of monomers that can form the (meth)acrylamide group-containing monomer unit, the carboxylic acid group-containing monomer unit, the acid anhydride monomer unit, the sulfonic acid group-containing monomer unit and the phosphoric acid group-containing monomer unit as the reactive monomer unit B2 are the same as the specific examples and preferred examples of monomers that can be used to form the respective monomer units as the above-mentioned reactive monomer unit B1.
[0109] Specific examples and preferred examples of the monomer that can form the epoxy-containing monomer unit as the reactive monomer unit B2 are the same as the specific examples and preferred examples of the monomer that can be used to form the epoxy-containing monomer unit as the reactive monomer unit A described above.
[0110] <Particle-shaped polymer (X)>
[0111] The granular polymer (X) can function as bonding particles that bond components to each other via a functional layer formed using the functional layer composition. In addition, the granular polymer (X) may be granular or in any other shape after bonding components to each other via a functional layer formed using the functional layer composition. Furthermore, the granular polymer (X) may be a crystalline polymer, a non-crystalline polymer, or a mixture thereof.
[0112] <<Volume average particle size>>
[0113] Furthermore, the volume average particle size of the particulate polymer (X) is larger than the volume average particle size of the particulate polymer (Y).
[0114] The volume average particle size of the particulate polymer (X) is not particularly limited as long as it is larger than the volume average particle size of the particulate polymer (Y), and is preferably 1 μm or more, more preferably 1.5 μm or more, further preferably 1.8 μm or more, further preferably 2.1 μm or more, and further preferably 3.5 μm or more, and preferably 10 μm or less, more preferably 8 μm or less, further preferably 6 μm or less, further preferably 5.5 μm or less, and further preferably 5 μm or less. If the volume average particle size of the particulate polymer (X) is greater than the above lower limit, the particulate polymer (X) protrudes from the surface in the thickness direction of the functional layer formed using the composition for the functional layer, and is easily in contact with the electrochemical element member, as a result of which the adhesion of the functional layer can be further improved. On the other hand, if the volume average particle size of the particulate polymer (X) is below the above upper limit, in the functional layer formed using the composition for a functional layer, the number of bonding points between the particulate polymer and materials other than the particulate polymer increases, and the falling off (so-called powdering) of the components constituting the functional layer can be suppressed, and as a result, the adhesion of the functional layer can be further improved. In addition, if the volume average particle size of the particulate polymer (X) is within the above-specified range, the heat resistance of the formed functional layer can be improved. That is, excellent heat resistance can be imparted to a laminate having the functional layer.
[0115] The volume average particle size of the particulate polymers (X) and (Y) can be adjusted by changing, for example, the composition and production conditions of the particulate polymers.
[0116] <<Composition>>
[0117] The particulate polymer (X) contains at least one of the reactive monomer unit A and the reactive monomer unit B described above.
[0118] [Reactive monomer unit A]
[0119] The particulate polymer (X) may contain an epoxy group-containing monomer unit or a hydroxyl group-containing monomer unit as the reactive monomer unit A. Furthermore, the particulate polymer (X) preferably contains an epoxy group-containing monomer unit as the reactive monomer unit A.
[0120] In the case where the granular polymer (X) contains reactive monomer units A, the content ratio of the reactive monomer units A in the granular polymer (X) is preferably 0.5% by mass or more, more preferably 1% by mass or more, more preferably 5% by mass or more, more preferably 8% by mass or more, and more preferably 12% by mass or more, preferably 30% by mass or less, more preferably 28% by mass or less, more preferably 27% by mass or less, and more preferably 26% by mass or less. If the content ratio of the reactive monomer units A in the granular polymer (X) is above the lower limit, a bond based on the reactive monomer units A and the reactive monomer units B is fully formed between the granular polymer (X) and the granular polymer (Y), and therefore, the adhesion of the functional layer formed using the composition for the functional layer can be further improved. On the other hand, if the content ratio of the reactive monomer units A in the granular polymer (X) is below the upper limit, the stability when preparing the granular polymer (X) can be improved.
[0121] In addition, when the granular polymer (X) contains reactive monomer units A, taking all monomer units in the granular polymer (X) as 100 mass %, the content ratio of the reactive monomer units A in the granular polymer (X) can be 15 mass % or more, 18 mass % or more, or 22 mass % or more, or less than 22 mass %, or less than 18 mass %, or less than 15 mass %, or less than 12 mass %.
[0122] In the present invention, the content ratio of each monomer unit in the polymer can be expressed as 1 H-NMR, 13 The measurement can be carried out by nuclear magnetic resonance (NMR) method such as C-NMR, X-ray photoelectron spectroscopy (XPS) method, etc.
[0123] [Reactive monomer unit B]
[0124] The particulate polymer (X) can contain reactive monomer units B.
[0125] In the case where the granular polymer (X) contains reactive monomer units B, the content ratio of the reactive monomer units B in the granular polymer (X) is preferably 0.5% by mass or more, more preferably 1% by mass or more, more preferably 1.5% by mass or more, more preferably 2% by mass or more, and more preferably 2.5% by mass or more, preferably 30% by mass or less, more preferably 20% by mass or less, more preferably 15% by mass or less, more preferably 10% by mass or less, and more preferably 5% by mass or less. If the content ratio of the reactive monomer units B in the granular polymer (X) is above the above lower limit, a bond based on the reactive monomer units A and the reactive monomer units B is fully formed between the granular polymer (X) and the granular polymer (Y), and therefore, the adhesion of the functional layer formed using the composition for the functional layer can be further improved. On the other hand, if the content ratio of the reactive monomer units B in the granular polymer (X) is below the above upper limit, the stability when preparing the granular polymer (X) can be improved.
[0126] -Reactive Monomer Unit B1-
[0127] Here, in the case where the granular polymer (Y) contains an epoxy group-containing monomer unit as the reactive monomer unit A, the granular polymer (X) contains a reactive monomer unit B1 as the reactive monomer unit B, and the above-mentioned reactive monomer unit B1 contains at least one selected from a (meth)acrylamide group-containing monomer unit, an acid anhydride monomer unit, a sulfonic acid group-containing monomer unit, a phosphoric acid group-containing monomer unit and an amino group-containing monomer unit.
[0128] The particulate polymer (X) may contain only one kind of the above-mentioned monomer units as the reactive monomer unit B1, or may contain two or more kinds of the above-mentioned monomer units at any ratio as the reactive monomer unit B1.
[0129] Furthermore, the particulate polymer (X) preferably contains a (meth)acrylamide group-containing monomer unit as the reactive monomer unit B1.
[0130] Furthermore, the particulate polymer (X) may further contain a carboxylic acid group-containing monomer unit as the reactive monomer unit B1.
[0131] The content ratio of the reactive monomer unit B1 in the particulate polymer (X) (i.e., the total content ratio of the (meth)acrylamide group-containing monomer unit, the acid anhydride monomer unit, the sulfonic acid group-containing monomer unit, the phosphoric acid group-containing monomer unit, the amino group-containing monomer unit, and the carboxylic acid group-containing monomer unit) is preferably 0.5% by mass or more, more preferably 1% by mass or more, further preferably 1.5% by mass or more, further preferably 2% by mass or more, and further preferably 2.5% by mass or more, preferably 30% by mass or less, more preferably 20% by mass or less, further preferably 15% by mass or less, further preferably 10% by mass or less, and further preferably 5% by mass or less. If the content ratio of the reactive monomer unit B1 in the particulate polymer (X) is not less than the above lower limit, the bonds based on the reactive monomer unit A and the reactive monomer unit B are sufficiently formed between the particulate polymer (X) and the particulate polymer (Y), and therefore, the adhesiveness of the functional layer formed using the composition for a functional layer can be further improved. On the other hand, when the content ratio of the reactive monomer unit B1 in the particulate polymer (X) is not more than the above upper limit, the stability during the preparation of the particulate polymer (X) can be improved.
[0132] The content ratio of the reactive monomer units B1 other than the carboxylic acid group-containing monomer units in the particulate polymer (X) (i.e., the total content ratio of the (meth)acrylamide group-containing monomer units, the acid anhydride monomer units, the sulfonic acid group-containing monomer units, the phosphoric acid group-containing monomer units, and the amino group-containing monomer units) is preferably 0.5% by mass or more, more preferably 1% by mass or more, further preferably 1.5% by mass or more, further preferably 2% by mass or more, and further preferably 2.5% by mass or more, and preferably 30% by mass or less, more preferably 20% by mass or less, further preferably 15% by mass or less, further preferably 10% by mass or less, and further preferably 5% by mass or less. If the content ratio of the reactive monomer units B1 other than the carboxylic acid group-containing monomer units in the particulate polymer (X) is not less than the above lower limit, the bonds based on the reactive monomer units A and the reactive monomer units B are sufficiently formed between the particulate polymer (X) and the particulate polymer (Y), and therefore, the adhesiveness of the functional layer formed using the composition for a functional layer can be further improved. On the other hand, when the content ratio of the reactive monomer units B1 other than the carboxylic acid group-containing monomer units in the particulate polymer (X) is not more than the above upper limit, the stability during the preparation of the particulate polymer (X) can be improved.
[0133] The content ratio of the carboxylic acid group-containing monomer unit as the reactive monomer unit B1 in the particulate polymer (X) can be appropriately adjusted within the range in which the desired effect of the present invention can be obtained.
[0134] Furthermore, of course, the particulate polymer (X) may not contain the carboxylic acid group-containing monomer unit as the reactive monomer unit B1.
[0135] -Reactive Monomer Unit B2-
[0136] When the granular polymer (Y) contains a hydroxyl group-containing monomer unit as the reactive monomer unit A, the granular polymer (X) contains a reactive monomer unit B2 as the reactive monomer unit B, and the above-mentioned reactive monomer unit B2 contains at least one selected from a (meth)acrylamide group-containing monomer unit, a carboxylic acid group-containing monomer unit, an acid anhydride monomer unit, a sulfonic acid group-containing monomer unit, a phosphoric acid group-containing monomer unit and an epoxy group-containing monomer unit.
[0137] The particulate polymer (X) may contain only one kind of the above-mentioned monomer units as the reactive monomer unit B2, or may contain two or more kinds of the above-mentioned monomer units at any ratio as the reactive monomer unit B2.
[0138] The content ratio of the reactive monomer unit B2 in the particulate polymer (X) (i.e., the total content ratio of the (meth)acrylamide group-containing monomer unit, the carboxylic acid group-containing monomer unit, the acid anhydride monomer unit, the sulfonic acid group-containing monomer unit, the phosphoric acid group-containing monomer unit and the epoxy group-containing monomer unit) is preferably 0.5% by mass or more, more preferably 1% by mass or more, further preferably 1.5% by mass or more, further preferably 2% by mass or more, further preferably 2.5% by mass or more, and is preferably 30% by mass or less, more preferably 20% by mass or less, further preferably 15% by mass or less, further preferably 10% by mass or less, further preferably 5% by mass or less.
[0139] If the content ratio of the reactive monomer unit B2 in the granular polymer (X) is above the above lower limit, bonds based on the reactive monomer unit A and the reactive monomer unit B are sufficiently formed between the granular polymer (X) and the granular polymer (Y), thereby further improving the adhesion of the functional layer formed using the functional layer composition.
[0140] On the other hand, when the content ratio of the reactive monomer unit B2 in the particulate polymer (X) is not more than the above upper limit, the stability during the preparation of the particulate polymer (X) can be improved.
[0141] [Other monomers]
[0142] The particulate polymer (X) may further contain monomer units other than the reactive monomer units A and B described above.
[0143] Furthermore, the particulate polymer (X) preferably further contains at least one selected from the group consisting of an aromatic monovinyl monomer unit, a cycloalkyl (meth)acrylate monomer unit, and an alkyl (meth)acrylate monomer unit. For example, the particulate polymer (X) may contain an aromatic monovinyl monomer unit and an alkyl (meth)acrylate monomer unit, or may contain a cycloalkyl (meth)acrylate monomer unit and an alkyl (meth)acrylate monomer unit.
[0144] Furthermore, the particulate polymer (X) preferably further contains a crosslinkable monomer unit.
[0145] The particulate polymer (X) is not particularly limited and may or may not contain monomer units other than the above-mentioned reactive monomer unit A, reactive monomer unit B, aromatic monovinyl monomer unit, (meth)acrylate cycloalkyl ester monomer unit, (meth)acrylate alkyl ester monomer unit and crosslinking monomer unit.
[0146] -Aromatic monovinyl monomer unit-
[0147] The aromatic monovinyl monomer capable of forming the aromatic monovinyl monomer unit is not particularly limited, and examples thereof include styrene, α-methylstyrene, styrenesulfonic acid, butoxystyrene, and vinylnaphthalene. Among them, styrene is preferred.
[0148] These aromatic monovinyl monomers may be used alone or in combination of two or more at any ratio.
[0149] Taking all monomer units in the granular polymer (X) as 100 mass %, the content ratio of the aromatic monovinyl monomer units in the granular polymer (X) is preferably 30 mass % or more, more preferably 45 mass % or more, further preferably 55 mass % or more, preferably 95 mass % or less, more preferably 90 mass % or less, further preferably 85 mass % or less, further preferably 75 mass % or less, further preferably 70 mass % or less, particularly preferably 65 mass % or less.
[0150] When the content ratio of the aromatic monovinyl monomer unit in the particulate polymer (X) is within the above-specified range, the adhesiveness of the functional layer formed using the functional layer composition can be further improved.
[0151] -(Meth)acrylic acid cycloalkyl ester monomer unit-
[0152] As the cycloalkyl (meth)acrylate monomer capable of forming the cycloalkyl (meth)acrylate monomer unit, cycloalkyl (meth)acrylates having a cycloalkyl group having 6 to 12 carbon atoms, such as cyclohexyl (meth)acrylate, can be preferably used.
[0153] Moreover, as a cycloalkyl (meth)acrylate monomer, one kind may be used alone, or two or more kinds may be used in combination at any ratio.
[0154] The content of the cycloalkyl (meth)acrylate monomer units in the particulate polymer (X) is preferably 30% by mass or more, more preferably 45% by mass or more, further preferably 55% by mass or more, and is preferably 95% by mass or less, more preferably 90% by mass or less, further preferably 85% by mass or less, and further preferably 80% by mass or less, based on 100% by mass of all monomer units in the particulate polymer (X).
[0155] When the content ratio of the cycloalkyl (meth)acrylate monomer unit in the particulate polymer (X) is within the above-specified range, the adhesiveness of the functional layer formed using the composition for a functional layer can be further improved.
[0156] -(Meth)acrylic acid alkyl ester monomer unit-
[0157] Examples of the alkyl (meth)acrylate monomers that can form the alkyl (meth)acrylate monomer units include butyl acrylates such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, and tert-butyl acrylate; alkyl acrylates such as octyl acrylates such as pentyl acrylate, hexyl acrylate, heptyl acrylate, and 2-ethylhexyl acrylate; nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, and stearyl acrylate; and butyl methacrylates such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, and tert-butyl methacrylate; octyl methacrylates such as pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, and 2-ethylhexyl methacrylate; nonyl methacrylate, decyl methacrylate, lauryl methacrylate, n-tetradecyl methacrylate, and stearyl methacrylate.
[0158] Among them, as the (meth)acrylic acid alkyl ester monomer, it is preferred to use a (meth)acrylic acid alkyl ester monomer in which the number of carbon atoms of the alkyl group is 4 or more and 18 or less, more preferably to use a (meth)acrylic acid alkyl ester monomer in which the number of carbon atoms of the alkyl group is 6 or more and 12 or less, further preferably to use a (meth)acrylic acid alkyl ester monomer in which the number of carbon atoms of the alkyl group is 6 or more and 10 or less, and 2-ethylhexyl acrylate is particularly preferred. If a (meth)acrylic acid alkyl ester monomer in which the number of carbon atoms of the alkyl group is within the above-specified range is used, the electrolyte swelling degree of the obtained granular polymer (X) can be appropriately reduced, and the output characteristics of the electrochemical element having the functional layer can be improved.
[0159] In addition, these alkyl (meth)acrylate monomers may be used alone or in combination of two or more at any ratio.
[0160] With all monomer units in the particulate polymer (X) being 100 mass %, the content of the alkyl (meth)acrylate monomer units in the particulate polymer (X) is preferably 2 mass % or more, more preferably 5 mass % or more, further preferably 10 mass % or more, and is preferably 60 mass % or less, more preferably 40 mass % or less, further preferably 30 mass % or less, further preferably 25 mass % or less, and further preferably 20 mass % or less.
[0161] If the content ratio of the (meth)acrylic acid alkyl ester monomer unit in the particulate polymer (X) is greater than the above lower limit, the glass transition temperature of the particulate polymer (X) can be prevented from being excessively lowered, and adhesion (so-called blocking) between the functional layer and the electrochemical element components can be suppressed when a laminate or electrochemical element having a functional layer formed using the composition for a functional layer is stored and transported in a wound state. That is, the anti-blocking property of the functional layer can be improved.
[0162] On the other hand, when the content ratio of the alkyl (meth)acrylate monomer unit in the particulate polymer (X) is not more than the above upper limit, the adhesiveness of the functional layer formed using the functional layer composition can be further improved.
[0163] - Cross-linking monomer unit-
[0164] Examples of the monomer capable of forming a crosslinkable monomer unit include crosslinkable monomers having two or more polymerizable reactive groups.
[0165] Examples of such crosslinking monomers include: (meth)acrylate monomers such as allyl methacrylate; aromatic divinyl monomers such as divinylbenzene and divinylnaphthalene; di(meth)acrylate monomers such as diethylene glycol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol diacrylate, and 1,3-butylene glycol diacrylate; tri(meth)acrylate monomers such as trimethylolpropane trimethacrylate and trimethylolpropane triacrylate, and the like.
[0166] Among them, allyl methacrylate and ethylene glycol dimethacrylate are preferably used as the crosslinking monomer.
[0167] These crosslinkable monomers may be used alone or in combination of two or more at any ratio.
[0168] Taking all monomer units in the particulate polymer (X) as 100 mass %, the content ratio of the crosslinkable monomer units in the particulate polymer (X) is preferably 0.05 mass % or more, more preferably 0.1 mass % or more, further preferably 0.15 mass % or more, and is preferably 5 mass % or less, more preferably 3 mass % or less, further preferably 2 mass % or less.
[0169] If the content ratio of the cross-linkable monomer unit in the particulate polymer (X) is greater than the above lower limit, the particulate polymer (X) is sufficiently cross-linked, thereby reducing the amount of the particulate polymer (X) eluted into the electrolyte and further improving the adhesiveness (especially wet adhesiveness) of the functional layer formed using the functional layer composition.
[0170] On the other hand, if the content ratio of the cross-linkable monomer unit in the particulate polymer (X) is below the above upper limit, excessive cross-linking of the particulate polymer (X) can be avoided, whereby the particulate polymer (X) can be easily deformed, thereby further improving the adhesiveness (especially wet adhesiveness) of the functional layer formed using the functional layer composition.
[0171] <Glass transition temperature>
[0172] The glass transition temperature of the particulate polymer (X) is preferably 40°C or higher, more preferably 50°C or higher, further preferably 60°C or higher, further preferably 65°C or higher, and is preferably 110°C or lower, more preferably 100°C or lower, further preferably 95°C or lower.
[0173] When the glass transition temperature of the particulate polymer (X) is not less than the above lower limit, thermal deformation of the particulate polymer (X) can be appropriately reduced, and therefore, the anti-blocking property of the functional layer formed using the functional layer composition can be improved.
[0174] On the other hand, if the glass transition temperature of the particulate polymer (X) is below the above upper limit, the thermal deformation of the particulate polymer (X) during hot pressing can be appropriately increased, thereby further improving the adhesiveness (especially dry adhesiveness) of the functional layer formed using the functional layer composition.
[0175] In the present invention, the glass transition temperature can be measured using the method described in Examples of the present specification.
[0176] <Electrolyte swelling degree>
[0177] The degree of swelling of the particulate polymer (X) with the electrolyte is preferably 120% or more, more preferably 130% or more, further preferably 140% or more, and is preferably 600% or less, more preferably 500% or less, further preferably 300% or less.
[0178] When the electrolyte swelling degree of the particulate polymer (X) is not less than the above lower limit, the particulate polymer (X) appropriately swells in the electrolyte, and thus the adhesiveness (particularly wet adhesiveness) of the functional layer formed using the functional layer composition can be further improved.
[0179] On the other hand, if the electrolyte swelling degree of the granular polymer (X) is below the above-mentioned upper limit, excessive swelling of the granular polymer (X) in the electrolyte can be suppressed, thereby avoiding interference with the movement of ions, and thus, the output characteristics of the electrochemical element having a functional layer formed using the functional layer composition can be improved.
[0180] <Method for producing granular polymer (X)>
[0181] The granular polymer (X) can be prepared by polymerizing a monomer composition containing the above-mentioned monomers in an aqueous solvent such as water. Here, unless otherwise specified, the content ratio of each monomer in the monomer composition is usually the same as the content ratio of each monomer unit in the granular polymer (X).
[0182] The polymerization method is not particularly limited, and any method such as suspension polymerization, emulsion polymerization coagulation, pulverization, etc. can be used. Among them, from the viewpoint of efficiently preparing the granular polymer (X), suspension polymerization and emulsion polymerization coagulation are preferred, and suspension polymerization is more preferred. In addition, as the polymerization reaction, any reaction such as free radical polymerization and living free radical polymerization can be used.
[0183] The monomer composition used for preparing the particulate polymer (X) may contain other additives such as a chain transfer agent, a polymerization regulator, a polymerization reaction retardant, a reactive fluidizing agent, a filler, a flame retardant, an antioxidant, a colorant, etc. in any amount.
[0184] Here, as an example, a method for producing a particulate polymer (X) by a suspension polymerization method will be described.
[0185] <<Preparation of granular polymer (X) by suspension polymerization>>
[0186] (1) Preparation of monomer composition
[0187] First, monomers capable of forming monomer units constituting the desired particulate polymer (X) and other compounding agents added as necessary are mixed to prepare a monomer composition.
[0188] (2) Droplet formation
[0189] Next, the monomer composition is dispersed in water, and a polymerization initiator is added to form droplets of the monomer composition. The method for forming the droplets is not particularly limited, and the droplets can be formed by shearing and stirring an aqueous medium containing the monomer composition using a disperser such as an emulsifying disperser.
[0190] When a disperser is used for forming droplets, the rotation speed of the disperser is preferably greater than 8000 rpm, more preferably 9500 rpm or more, further preferably 11000 rpm or more, preferably less than 15000 rpm, more preferably 14000 rpm or less, further preferably 13000 rpm or less. If the rotation speed of the disperser is within the above-specified range, the volume average particle size of the particulate polymer (X) can be easily adjusted.
[0191] Examples of the polymerization initiator include oil-soluble polymerization initiators such as tert-butyl peroxy-2-ethylhexanoate and azobisisobutyronitrile. The polymerization initiator may be added after the monomer composition is dispersed in water and before droplets are formed, or may be added to the monomer composition before it is dispersed in water.
[0192] Furthermore, from the viewpoint of stabilizing the formed droplets of the monomer composition in water, it is preferred to add a dispersion stabilizer to water to form the droplets of the monomer composition. In this case, as the dispersion stabilizer, for example, metal hydroxides such as magnesium hydroxide, sodium dodecylbenzenesulfonate, etc. can be used.
[0193] (3) Aggregation
[0194] Then, after the droplets of the monomer composition are formed, the water containing the formed droplets is heated to initiate polymerization, thereby forming a particulate polymer (X) in water. At this time, the polymerization reaction temperature is preferably 50° C. or higher and 95° C. or lower. In addition, the polymerization reaction time is preferably 1 hour or higher and 10 hours or lower, preferably 8 hours or lower, and more preferably 6 hours or lower.
[0195] Alternatively, a second monomer composition having a composition different from that of the above monomer composition (hereinafter referred to as “first monomer composition”) may be prepared, and the second monomer composition may be added to the water containing the droplets during the above polymerization.
[0196] Here, when a monomer capable of forming a reactive monomer unit A (hereinafter referred to as "reactive monomer A") is used in preparing the particulate polymer (X), it is preferred that the content of the reactive monomer A in the second monomer composition is higher than the content of the reactive monomer A in the first monomer composition. If the content of the reactive monomer A in the second monomer composition is higher than the content of the reactive monomer A in the first monomer composition, the ratio of the amount of the reactive monomer unit A present on the particle surface to the total amount of the reactive monomer unit A contained in the entire particle of the particulate polymer (X) can be appropriately increased, and the adhesiveness of the functional layer formed using the functional layer composition can be further improved.
[0197] Furthermore, when a monomer capable of forming a reactive monomer unit B (hereinafter referred to as "reactive monomer B") is used in preparing the particulate polymer (X), it is preferred that the content of the reactive monomer B in the second monomer composition is higher than the content of the reactive monomer B in the first monomer composition. If the content of the reactive monomer B in the second monomer composition is higher than the content of the reactive monomer B in the first monomer composition, the ratio of the amount of the reactive monomer unit B present on the particle surface to the total amount of the reactive monomer unit B contained in the entire particle of the particulate polymer (X) can be appropriately increased, and the adhesiveness of the functional layer formed using the functional layer composition can be further improved.
[0198] It should be noted that the content ratio of each monomer in the first monomer composition is different from the content ratio of each monomer unit in the granular polymer (X), and the content ratio of each monomer in the second monomer composition is different from the content ratio of each monomer unit in the granular polymer (X). The content ratio of each monomer relative to the total amount of the monomer in the first monomer composition and the monomer in the second monomer composition is the same as the content ratio of each monomer unit in the granular polymer (X).
[0199] (4) Cleaning, filtering, dehydration and drying processes
[0200] After completion of the polymerization, the water containing the particulate polymer (X) is washed, filtered and dried according to a conventional method, thereby obtaining the particulate polymer (X).
[0201] <Particle-shaped polymer (Y)>
[0202] The granular polymer (Y) can act as a bonding material that bonds the granular polymer (X) and the non-conductive heat-resistant particles contained in the functional layer to each other and prevents them from falling off. In addition, after the components are bonded to each other via the functional layer formed using the functional layer composition, the granular polymer (Y) may be granular or in any other shape.
[0203] <<Volume average particle size>>
[0204] The volume average particle size of the particulate polymer (Y) is smaller than the volume average particle size of the particulate polymer (X).
[0205] The volume average particle size of the particulate polymer (Y) is not particularly limited as long as it is smaller than the volume average particle size of the particulate polymer (X), and is preferably 0.08 μm or more, more preferably 0.1 μm or more, further preferably 0.12 μm or more, preferably 0.5 μm or less, more preferably 0.45 μm or less, and further preferably 0.4 μm or less.
[0206] When the volume average particle size of the particulate polymer (Y) is not less than the above lower limit, a sufficient area in contact with the particulate polymer (X) can be obtained, and thus the adhesiveness of the functional layer formed using the functional layer composition can be further improved.
[0207] On the other hand, if the volume average particle size of the granular polymer (Y) is below the above upper limit, it is possible to fully ensure the gaps between the components in the functional layer formed using the functional layer composition and improve the air permeability of the functional layer, thereby improving the ion conductivity, and therefore, the output characteristics of the electrochemical element having the functional layer can be improved.
[0208] In the present invention, the volume average particle size of the particulate polymer (Y) can be measured by the method described in Examples of the present specification.
[0209] <<Composition>>
[0210] The particulate polymer (Y) contains at least one of the reactive monomer unit A and the reactive monomer unit B described above.
[0211] [Reactive monomer unit A]
[0212] The particulate polymer (Y) may contain an epoxy-containing monomer unit or a hydroxyl-containing monomer unit as the reactive monomer unit A. When the particulate polymer (Y) contains the reactive monomer unit A, the particulate polymer (Y) preferably contains an epoxy-containing monomer unit as the reactive monomer unit A.
[0213] In the case where the granular polymer (Y) contains reactive monomer units A, the content ratio of the reactive monomer units A in the granular polymer (Y) is preferably 0.5% by mass or more, more preferably 1% by mass or more, more preferably 5% by mass or more, more preferably 8% by mass or more, preferably 30% by mass or less, more preferably 28% by mass or less, more preferably 27% by mass or less, and more preferably 26% by mass or less. If the content ratio of the reactive monomer units A in the granular polymer (Y) is above the above lower limit, a bond based on the reactive monomer units A and the reactive monomer units B is fully formed between the granular polymer (X) and the granular polymer (Y), and therefore, the adhesion of the functional layer formed using the functional layer composition can be further improved. On the other hand, if the content ratio of the reactive monomer units A in the granular polymer (Y) is below the above upper limit, the stability when preparing the granular polymer (Y) can be improved.
[0214] In addition, when the granular polymer (Y) contains reactive monomer units A, the content ratio of the reactive monomer units A in the granular polymer (Y) can be 10% by mass or more, 12% by mass or more, or 15% by mass or more, and can be 22% by mass or less, 18% by mass or less, 16% by mass or less, or 15% by mass or less, based on the total monomer units in the granular polymer (Y) as 100% by mass.
[0215] [Reactive monomer unit B]
[0216] The particulate polymer (Y) can contain reactive monomer units B.
[0217] In the case where the granular polymer (Y) contains reactive monomer units B, the content ratio of the reactive monomer units B in the granular polymer (Y) is preferably 0.5% by mass or more, more preferably 1% by mass or more, more preferably 2% by mass or more, more preferably 3% by mass or more, and more preferably 4% by mass or more, preferably 30% by mass or less, more preferably 20% by mass or less, more preferably 15% by mass or less, more preferably 10% by mass or less, and more preferably 8% by mass or less. If the content ratio of the reactive monomer units B in the granular polymer (Y) is above the above lower limit, a bond based on the reactive monomer units A and the reactive monomer units B is fully formed between the granular polymer (X) and the granular polymer (Y), and therefore, the adhesion of the functional layer formed using the functional layer composition can be further improved. On the other hand, if the content ratio of the reactive monomer units B in the granular polymer (Y) is below the above upper limit, the stability when preparing the granular polymer (Y) can be improved.
[0218] -Reactive Monomer Unit B1-
[0219] Here, in the case where the granular polymer (X) contains an epoxy group-containing monomer unit as the reactive monomer unit A, the granular polymer (Y) contains a reactive monomer unit B1 as the reactive monomer unit B, and the above-mentioned reactive monomer unit B1 contains at least one selected from a (meth)acrylamide group-containing monomer unit, an acid anhydride monomer unit, a sulfonic acid group-containing monomer unit, a phosphoric acid group-containing monomer unit and an amino group-containing monomer unit.
[0220] The particulate polymer (Y) may contain only one kind of the above-mentioned monomer units as the reactive monomer unit B1, or may contain two or more kinds of the above-mentioned monomer units at any ratio as the reactive monomer unit B1.
[0221] Furthermore, the particulate polymer (Y) preferably contains a (meth)acrylamide group-containing monomer unit as the reactive monomer unit B1.
[0222] Furthermore, the particulate polymer (Y) preferably further contains a carboxylic acid group-containing monomer unit as the reactive monomer unit B1.
[0223] The content ratio of the reactive monomer unit B1 in the particulate polymer (Y) (i.e., the total content ratio of the (meth)acrylamide group-containing monomer unit, the acid anhydride monomer unit, the sulfonic acid group-containing monomer unit, the phosphoric acid group-containing monomer unit, the amino group-containing monomer unit, and the carboxylic acid group-containing monomer unit) is preferably 0.5% by mass or more, more preferably 1% by mass or more, further preferably 2% by mass or more, further preferably 3% by mass or more, and further preferably 4% by mass or more, preferably 30% by mass or less, more preferably 20% by mass or less, further preferably 15% by mass or less, further preferably 10% by mass or less, and further preferably 8% by mass or less. If the content ratio of the reactive monomer unit B1 in the particulate polymer (Y) is not less than the above lower limit, the bond based on the reactive monomer unit A and the reactive monomer unit B is sufficiently formed between the particulate polymer (X) and the particulate polymer (Y), and therefore, the adhesiveness of the functional layer formed using the composition for a functional layer can be further improved. On the other hand, when the content ratio of the reactive monomer unit B1 in the particulate polymer (Y) is not more than the above upper limit, the stability during the preparation of the particulate polymer (Y) can be improved.
[0224] With all monomer units in the particulate polymer (Y) being 100 mass%, the content ratio of the reactive monomer units B1 other than the carboxylic acid group-containing monomer units in the particulate polymer (Y) (i.e., the total content ratio of the (meth)acrylamide group-containing monomer units, the acid anhydride monomer units, the sulfonic acid group-containing monomer units, the phosphoric acid group-containing monomer units and the amino group-containing monomer units) is preferably 0.4 mass% or more, more preferably 0.8 mass% or more, further preferably 1.5 mass% or more, further preferably 2.5 mass% or more, further preferably 3.5 mass% or more, preferably 20 mass% or less, more preferably 15 mass% or less, further preferably 13 mass% or less, further preferably 8.5 mass% or less, further preferably 6.8 mass% or less. If the content ratio of the reactive monomer unit B1 other than the carboxylic acid group-containing monomer unit in the granular polymer (Y) is not less than the above lower limit, the bond based on the reactive monomer unit A and the reactive monomer unit B is sufficiently formed between the granular polymer (X) and the granular polymer (Y), and therefore, the adhesiveness of the functional layer formed using the functional layer composition can be further improved. On the other hand, if the content ratio of the reactive monomer unit B1 other than the carboxylic acid group-containing monomer unit in the granular polymer (Y) is not more than the above upper limit, the stability when preparing the granular polymer (Y) can be improved.
[0225] Taking all monomer units in the granular polymer (Y) as 100 mass %, the content of the carboxylic acid group-containing monomer unit as the reactive monomer unit B1 in the granular polymer (Y) is preferably 0.1 mass % or more, more preferably 0.2 mass % or more, further preferably 0.5 mass % or more, preferably 10 mass % or less, more preferably 5 mass % or less, further preferably 2 mass % or less, further preferably 1.5 mass % or less, and further preferably 1.2 mass % or less. If the content of the carboxylic acid group-containing monomer unit as the reactive monomer unit B1 in the granular polymer (Y) is within the above-specified range, bonds based on the reactive monomer unit A and the reactive monomer unit B are sufficiently formed between the granular polymer (X) and the granular polymer (Y), and therefore, the adhesiveness of the functional layer formed using the composition for the functional layer can be further improved.
[0226] -Reactive Monomer Unit B2-
[0227] When the granular polymer (X) contains a hydroxyl group-containing monomer unit as the reactive monomer unit A, the granular polymer (Y) contains a reactive monomer unit B2 as the reactive monomer unit B, and the above-mentioned reactive monomer unit B2 contains at least one selected from a (meth)acrylamide group-containing monomer unit, a carboxylic acid group-containing monomer unit, an acid anhydride monomer unit, a sulfonic acid group-containing monomer unit, a phosphoric acid group-containing monomer unit and an epoxy group-containing monomer unit.
[0228] The particulate polymer (Y) may contain only one kind of the above-mentioned monomer units as the reactive monomer unit B2, or may contain two or more kinds of the above-mentioned monomer units at any ratio as the reactive monomer unit B2.
[0229] Furthermore, the particulate polymer (Y) preferably contains at least a (meth)acrylamide group-containing monomer unit as the reactive monomer unit B2, and more preferably contains a (meth)acrylamide group-containing monomer unit and a carboxylic acid group-containing monomer unit as the reactive monomer unit B2.
[0230] The content ratio of the reactive monomer unit B2 in the particulate polymer (Y) (i.e., the total content ratio of the (meth)acrylamide group-containing monomer unit, the carboxylic acid group-containing monomer unit, the acid anhydride monomer unit, the sulfonic acid group-containing monomer unit, the phosphoric acid group-containing monomer unit, and the epoxy group-containing monomer unit) is preferably 0.5% by mass or more, more preferably 1% by mass or more, further preferably 2% by mass or more, further preferably 3% by mass or more, and further preferably 4% by mass or more, and preferably 30% by mass or less, more preferably 20% by mass or less, further preferably 15% by mass or less, further preferably 10% by mass or less, and further preferably 8% by mass or less. If the content ratio of the reactive monomer unit B2 in the particulate polymer (Y) is greater than the above lower limit, a bond based on the reactive monomer unit A and the reactive monomer unit B is sufficiently formed between the particulate polymer (X) and the particulate polymer (Y), and therefore, the adhesiveness of the functional layer formed using the composition for a functional layer can be further improved. On the other hand, when the content ratio of the reactive monomer unit B2 in the particulate polymer (Y) is not more than the above upper limit, the stability during the preparation of the particulate polymer (Y) can be improved.
[0231] [Other monomer units]
[0232] The particulate polymer (Y) may further contain monomer units other than the above-mentioned reactive monomer units A and reactive monomer units B (hereinafter, sometimes referred to as "other monomer units").
[0233] Examples of other monomer units that may be contained in the particulate polymer (Y) include aromatic monovinyl monomer units, (meth)acrylic acid alkyl ester monomer units, nitrile group-containing monomer units, conjugated diene monomer units, and crosslinkable monomer units.
[0234] The particulate polymer (Y) may contain only one of the above-mentioned monomer units as the other monomer unit, or may contain two or more of them at any ratio as the other monomer unit.
[0235] Furthermore, the particulate polymer (Y) preferably contains at least one of an aromatic monovinyl monomer unit and an alkyl (meth)acrylate monomer unit as other monomer units.
[0236] As for the particulate polymer (Y) that can be preferably used in the composition for the functional layer of the present invention, for example, it can contain at least a (meth)acrylic acid alkyl ester monomer unit, a nitrile group-containing monomer unit and a crosslinking monomer unit as other monomer units, and can also contain at least an aromatic monovinyl monomer unit, a (meth)acrylic acid alkyl ester monomer unit and a crosslinking monomer unit as other monomer units, and can also contain an aromatic monovinyl monomer unit and a conjugated diene monomer unit as other monomer units.
[0237] In addition, the granular polymer (Y) is not particularly limited and may contain monomer units other than the above-mentioned reactive monomer unit A, reactive monomer unit B, aromatic monovinyl monomer unit, (meth) alkyl acrylate monomer unit, nitrile group-containing monomer unit, conjugated diene monomer unit and crosslinking monomer unit, or may not contain them.
[0238] -Aromatic monovinyl monomer unit-
[0239] Specific examples and preferred examples of the aromatic monovinyl monomer capable of forming the aromatic monovinyl monomer unit in the particulate polymer (Y) are the same as the specific examples and preferred examples of the aromatic monovinyl monomer capable of forming the aromatic monovinyl monomer unit in the particulate polymer (X) described above.
[0240] Taking all monomer units in the granular polymer (Y) as 100 mass %, the content ratio of the aromatic monovinyl monomer units in the granular polymer (Y) is preferably 10 mass % or more, more preferably 15 mass % or more, preferably 25 mass % or more, preferably 60 mass % or less, more preferably 50 mass % or less, further preferably 40 mass % or less.
[0241] When the content ratio of the aromatic monovinyl monomer unit in the particulate polymer (Y) is within the above-specified range, the adhesiveness of the functional layer formed using the functional layer composition can be further improved.
[0242] -(Meth)acrylic acid alkyl ester monomer unit-
[0243] Specific examples of the alkyl (meth)acrylate monomer capable of forming the alkyl (meth)acrylate monomer unit in the particulate polymer (Y) are the same as the specific examples of the alkyl (meth)acrylate monomer capable of forming the alkyl (meth)acrylate monomer unit in the particulate polymer (X).
[0244] Among them, as the (meth)acrylic acid alkyl ester monomer, n-butyl acrylate, 2-ethylhexyl acrylate and methyl methacrylate are preferred, and n-butyl acrylate is more preferred.
[0245] Taking all monomer units in the particulate polymer (Y) as 100 mass %, the content ratio of the (meth)acrylic acid alkyl ester monomer units in the particulate polymer (Y) is preferably 50 mass % or more, more preferably 55 mass % or more, further preferably 58 mass % or more, and is preferably 98 mass % or less, more preferably 97 mass % or less, further preferably 96 mass % or less.
[0246] When the content ratio of the alkyl (meth)acrylate monomer unit in the particulate polymer (Y) is within the above-specified range, the adhesiveness of the functional layer formed using the composition for a functional layer can be further improved.
[0247] The content of the alkyl (meth)acrylate monomer units in the particulate polymer (Y) may be 70% by mass or more, or 80% by mass or more, and may be 93% by mass or less, or 92% by mass or less.
[0248] -Nitrile-containing monomer unit-
[0249] Examples of nitrile group-containing monomers that can form nitrile group-containing monomer units include α,β-ethylenically unsaturated nitrile monomers. Specifically, the α,β-ethylenically unsaturated nitrile monomers are not particularly limited as long as they are α,β-ethylenically unsaturated compounds having nitrile groups, and examples thereof include acrylonitrile; α-halogenated acrylonitriles such as α-chloroacrylonitrile and α-bromoacrylonitrile; α-alkyl acrylonitriles such as methacrylonitrile and α-ethylacrylonitrile, and the like.
[0250] Among them, acrylonitrile is preferably used as the nitrile group-containing monomer.
[0251] These nitrile group-containing monomers may be used alone or in combination of two or more at any ratio.
[0252] Taking all monomer units in the granular polymer (Y) as 100 mass %, the content ratio of the nitrile group-containing monomer units in the granular polymer (Y) is preferably 0.1 mass % or more, more preferably 0.5 mass % or more, further preferably 1 mass % or more, preferably 20 mass % or less, more preferably 15 mass % or less, further preferably 10 mass % or less.
[0253] When the content ratio of the nitrile group-containing monomer unit in the particulate polymer (Y) is within the above-specified range, the adhesiveness of the functional layer formed using the functional layer composition can be further improved.
[0254] In addition, taking all monomer units in the granular polymer (Y) as 100 mass %, the content ratio of the nitrile group-containing monomer units in the granular polymer (Y) can be 2 mass % or more, 3 mass % or more, or 4 mass % or more, and can be 8 mass % or less, 6 mass % or less, or 4 mass % or less.
[0255] -Conjugated diene monomer unit-
[0256] Examples of the conjugated diene monomer capable of forming the conjugated diene monomer unit include aliphatic conjugated diene monomers such as 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, and 2-chloro-1,3-butadiene.
[0257] Among them, 1,3-butadiene is preferably used as the conjugated diene monomer.
[0258] These conjugated diene monomers may be used alone or in combination of two or more at any ratio.
[0259] Taking all monomer units in the particulate polymer (Y) as 100 mass %, the content ratio of the conjugated diene monomer units in the particulate polymer (Y) is preferably 30 mass % or more, more preferably 40 mass % or more, further preferably 50 mass % or more, preferably 80 mass % or less, more preferably 75 mass % or less, further preferably 70 mass % or less.
[0260] When the content ratio of the conjugated diene monomer unit in the particulate polymer (Y) is within the above-specified range, the adhesiveness of the functional layer formed using the composition for a functional layer can be further improved.
[0261] - Cross-linking monomer unit-
[0262] Specific examples and preferred examples of the crosslinkable monomer capable of forming the crosslinkable monomer unit in the particulate polymer (Y) are the same as the specific examples and preferred examples of the crosslinkable monomer capable of forming the crosslinkable monomer unit in the particulate polymer (X) described above.
[0263] Taking all monomer units in the particulate polymer (Y) as 100 mass %, the content ratio of the crosslinkable monomer units in the particulate polymer (Y) is preferably 0.05 mass % or more, more preferably 0.1 mass % or more, further preferably 0.15 mass % or more, and is preferably 5 mass % or less, more preferably 3 mass % or less, further preferably 2 mass % or less.
[0264] When the content ratio of the crosslinkable monomer unit in the particulate polymer (Y) is within the above-specified range, the adhesiveness of the functional layer formed using the composition for a functional layer can be further improved.
[0265] In addition, taking all monomer units in the granular polymer (Y) as 100 mass %, the content ratio of the crosslinkable monomer units in the granular polymer (Y) can be 0.2 mass % or more, 0.5 mass % or more, 1 mass % or more, 1.5 mass % or more, and can be 1.5 mass % or less, 1 mass % or less, 0.5 mass % or less, or 0.2 mass % or less.
[0266] <Glass transition temperature>
[0267] The glass transition temperature of the particulate polymer (Y) is preferably -100°C or higher, more preferably -90°C or higher, further preferably -80°C or higher, and is preferably lower than 30°C, more preferably 20°C or lower, further preferably 15°C or lower.
[0268] When the glass transition temperature of the particulate polymer (Y) is not less than the above lower limit, the adhesiveness of the functional layer formed using the composition for a functional layer can be further improved, and the anti-blocking property of the functional layer can be improved.
[0269] On the other hand, when the glass transition temperature of the particulate polymer (Y) is lower than the above upper limit or is equal to or lower than the above upper limit, the flexibility of the functional layer can be improved.
[0270] <Method for producing granular polymer (Y)>
[0271] In addition, the preparation method of the granular polymer (Y) is not particularly limited, and for example, it can be prepared by polymerizing a monomer composition containing the above-mentioned monomers in an aqueous solvent such as water. Here, the content ratio of each monomer in the monomer composition is usually the same as the content ratio of each monomer unit in the granular polymer (Y).
[0272] The polymerization method and polymerization reaction are not particularly limited, and for example, the polymerization method and polymerization reaction exemplified in the method for producing the particulate polymer (X) can be used.
[0273] <Content of granular polymer (Y)>
[0274] The content of the particulate polymer (Y) in the composition for the functional layer is preferably 10 parts by mass or more, more preferably 25 parts by mass or more, further preferably 50 parts by mass or more, further preferably 80 parts by mass or more, and is preferably 200 parts by mass or less, more preferably 180 parts by mass or less, further preferably 150 parts by mass or less, further preferably 120 parts by mass or less, relative to 100 parts by mass of the particulate polymer (X).
[0275] When the content of the particulate polymer (Y) is not less than the above lower limit, the adhesiveness of the functional layer formed using the composition for a functional layer can be further improved, and the heat resistance of the functional layer can be improved.
[0276] On the other hand, if the content of the granular polymer (Y) is below the above upper limit, it is possible to fully ensure the gaps between the components in the functional layer formed using the functional layer composition and improve the air permeability of the functional layer, thereby improving the ion conductivity, and therefore, the output characteristics of the electrochemical element having the functional layer can be improved.
[0277] In addition, from the viewpoint of further improving the adhesion of the functional layer formed using the functional layer composition and further improving the heat resistance of the functional layer, the content of the granular polymer (Y) in the functional layer composition is further preferably 95 parts by mass or more relative to 100 parts by mass of the granular polymer (X), further preferably 100 parts by mass or more, and particularly preferably 105 parts by mass or more.
[0278] In addition, from the viewpoint of further improving the air permeability of the functional layer formed using the functional layer composition and further improving the output characteristics of the electrochemical element having the functional layer, the content of the granular polymer (Y) in the functional layer composition is further preferably 94 parts by mass or less, further preferably 90 parts by mass or less, and particularly preferably 80 parts by mass or less relative to 100 parts by mass of the granular polymer (X).
[0279] When the functional layer composition contains the non-conductive heat-resistant particles described later, the content of the particulate polymer (Y) in the functional layer composition is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, further preferably 2 parts by mass or more, further preferably 2.5 parts by mass or more, and preferably 6 parts by mass or less, more preferably 4.5 parts by mass or less, further preferably 4 parts by mass or less, relative to 100 parts by mass of the non-conductive heat-resistant particles.
[0280] When the content of the particulate polymer (Y) is not less than the above lower limit, the adhesiveness of the functional layer formed using the composition for a functional layer can be further improved, and the heat resistance of the functional layer can be improved.
[0281] On the other hand, if the content of the granular polymer (Y) is below the above upper limit, it is possible to fully ensure the gaps between the components in the functional layer formed using the functional layer composition and improve the air permeability of the functional layer, thereby improving the ion conductivity, and therefore, the output characteristics of the electrochemical element having the functional layer can be improved.
[0282] <Non-conductive heat-resistant particles>
[0283] The composition for a functional layer of the present invention preferably further comprises non-conductive heat-resistant particles. If the composition for a functional layer further comprises non-conductive heat-resistant particles, the heat resistance of the functional layer can be improved using the composition for a functional layer.
[0284] In this specification, "non-conductive heat-resistant particles" refer to non-conductive fine particles having a heat-resistant temperature of 200° C. or higher, and "heat-resistant temperature" refers to a temperature at which no substantial physical changes such as thermal deformation occur.
[0285] The non-conductive heat-resistant particles are not particularly limited as long as they are fine particles having a heat-resistant temperature of 200° C. or higher, are electrochemically stable, and have electrical insulating properties, but inorganic particles are preferred.
[0286] Since inorganic particles have a large specific gravity, when a functional layer is formed, for example, by coating a composition for a functional layer containing inorganic particles on a substrate, the granular polymer (X) tends to protrude more than the inorganic particles on the surface in the thickness direction of the functional layer, thereby further improving the adhesion of the functional layer.
[0287] Here, as the material of inorganic particles, it is preferred that the material exists stably and is electrochemically stable in the use environment of the electrochemical element, and for example, oxide particles such as aluminum oxide (Alumina), aluminum oxide hydrate (boehmite (AlOOH)), gibbsite (Al(OH3)), silicon oxide, magnesium oxide (Magnesia), magnesium hydroxide, calcium oxide, titanium oxide (Titania), barium titanate (BaTiO3), zirconium oxide (ZrO), aluminum oxide-silicon dioxide composite oxide; nitride particles such as aluminum nitride and boron nitride; covalently bonded grains such as silicon and diamond; insoluble ionic grains such as barium sulfate, calcium fluoride, and barium fluoride; clay particles such as talc and montmorillonite, etc. Among these, aluminum oxide, aluminum oxide hydrate (boehmite), magnesium hydroxide and barium sulfate are more preferred, and aluminum oxide is further preferred. In addition, these particles can be subjected to element replacement, surface treatment, solid solution, etc. as needed.
[0288] These inorganic particles may be used alone or in combination of two or more at any ratio.
[0289] <<Volume average particle size of non-conductive heat-resistant particles>>
[0290] The volume average particle size (D50) of the non-conductive heat-resistant particles is preferably 0.1 μm or more, more preferably 0.2 μm or more, further preferably 0.25 μm or more, and is preferably 1.5 μm or less, more preferably 1.0 μm or less, further preferably 0.8 μm or less.
[0291] If the volume average particle size of the non-conductive heat-resistant particles is greater than the above lower limit, it is possible to prevent the non-conductive heat-resistant particles from being excessively filled at a high density in the functional layer formed using the functional layer composition. As a result, the air permeability of the functional layer is improved, the ion conductivity can be improved, and therefore, the output characteristics of the electrochemical element having the functional layer can be improved.
[0292] On the other hand, if the volume average particle size of the non-conductive heat-resistant particles is below the above upper limit, the non-conductive heat-resistant particles can be appropriately filled in the functional layer formed using the functional layer composition at a high density. Thus, even when the functional layer is thinned, the functional layer can exert sufficient heat resistance. As a result, the electrochemical element having the functional layer can be thinned and have a high capacity.
[0293] In the present invention, the volume average particle size of the non-conductive heat-resistant particles can be measured using the method described in Examples of the present specification.
[0294] <<Volume ratio of non-conductive heat-resistant particles to granular polymer (X)>>
[0295] The volume ratio of the non-conductive heat-resistant particles to the particulate polymer (X) in the functional layer composition (non-conductive heat-resistant particles / particulate polymer (X)) is preferably 40 / 60 or more, more preferably 50 / 50 or more, further preferably 60 / 40 or more, further preferably 70 / 30 or more, further preferably 75 / 25 or more, further preferably 80 / 20 or more, particularly preferably 85 / 15 or more, preferably 99 / 1 or less, more preferably 97 / 3 or less, further preferably 95 / 5 or less, further preferably 92 / 8 or less.
[0296] If the volume ratio of the non-conductive heat-resistant particles to the granular polymer (X) in the composition for a functional layer (non-conductive heat-resistant particles / granular polymer (X)) is greater than the above lower limit, the non-conductive heat-resistant particles are sufficiently present in the functional layer formed using the composition for a functional layer, thereby being able to improve the heat resistance of the functional layer.
[0297] On the other hand, if the volume ratio of the non-conductive heat-resistant particles to the granular polymer (X) in the composition for the functional layer (non-conductive heat-resistant particles / granular polymer (X)) is below the above upper limit, the granular polymer (X) is sufficiently present in the functional layer formed using the composition for the functional layer, and therefore, the adhesion of the functional layer can be further improved.
[0298] <<Mass ratio of non-conductive heat-resistant particles to granular polymer (X)>>
[0299] The mass ratio of the non-conductive heat-resistant particles to the granular polymer (X) in the composition for the functional layer (non-conductive heat-resistant particles / granular polymer (X)) is preferably 50 / 50 or more, more preferably 60 / 40 or more, further preferably 70 / 30 or more, further preferably 80 / 20 or more, further preferably 90 / 10 or more, further preferably 95 / 5 or more, preferably 999 / 1 or less, more preferably 998 / 2 or less, further preferably 995 / 5 or less, further preferably 99 / 1 or less.
[0300] If the mass ratio of the non-conductive heat-resistant particles to the granular polymer (X) in the composition for a functional layer (non-conductive heat-resistant particles / granular polymer (X)) is greater than the above lower limit, the non-conductive heat-resistant particles are sufficiently present in the functional layer formed using the composition for a functional layer, thereby being able to improve the heat resistance of the functional layer.
[0301] On the other hand, if the mass ratio of the non-conductive heat-resistant particles to the granular polymer (X) in the composition for the functional layer (non-conductive heat-resistant particles / granular polymer (X)) is below the above upper limit, the granular polymer (X) is sufficiently present in the functional layer formed using the composition for the functional layer, and therefore, the adhesion of the functional layer can be further improved.
[0302] <<Mass ratio of non-conductive heat-resistant particles to granular polymer (X) and granular polymer (Y)>>
[0303] The mass ratio of the content of the non-conductive heat-resistant particles to the total content of the particulate polymer (X) and the particulate polymer (Y) in the composition for the functional layer (non-conductive heat-resistant particles / particulate polymer (X) and particulate polymer (Y)) is preferably 40 / 60 or more, more preferably 50 / 50 or more, further preferably 60 / 40 or more, further preferably 70 / 30 or more, further preferably 85 / 15 or more, further preferably 90 / 10 or more, particularly preferably 93 / 7 or more, preferably 999 / 1 or less, more preferably 998 / 2 or less, further preferably 995 / 5 or less, further preferably 99 / 1 or less.
[0304] If the mass ratio of the content of the non-conductive heat-resistant particles in the composition for the functional layer to the total content of the granular polymer (X) and the granular polymer (Y) (non-conductive heat-resistant particles / granular polymer (X) and granular polymer (Y)) is greater than the above lower limit, the non-conductive heat-resistant particles are sufficiently present in the functional layer formed using the composition for the functional layer, and thus the heat resistance of the functional layer can be improved. Furthermore, by appropriately reducing the total content of the granular polymer (X) and the granular polymer (Y), the air permeability of the functional layer formed using the composition for the functional layer is improved, and the ion conductivity can be improved, so that the output characteristics of the electrochemical element having the functional layer can be improved.
[0305] On the other hand, if the mass ratio of the content of the non-conductive heat-resistant particles in the composition for the functional layer to the total content of the granular polymer (X) and the granular polymer (Y) (non-conductive heat-resistant particles / granular polymer (X) and granular polymer (Y)) is below the above-mentioned upper limit, the adhesion of the functional layer formed using the composition for the functional layer can be further improved.
[0306] <Amine compounds>
[0307] The composition for a functional layer of the present invention preferably further contains an amine compound. If the composition for a functional layer further contains an amine compound, the storage stability of the composition for a functional layer can be improved.
[0308] Here, as amine compound, it is not particularly limited, for example, hydroxylamine sulfate, diethylhydroxylamine, dimethylhydroxylamine, dipropylhydroxylamine, isopropylhydroxylamine, isothiazolinyl compounds, etc. can be cited. Among them, from the viewpoint of being able to further improve the storage stability of the composition for functional layer, isothiazolinyl compounds are preferred. In addition, as isothiazolinyl compounds, for example, 1,2-benzo-4-isothiazoline-3-one, 2-methyl-4-isothiazoline-3-one, etc. can be cited.
[0309] These amine compounds may be used alone or in combination of two or more at any ratio.
[0310] The content of the amine compound is preferably 0.3 parts by mass or more, more preferably 0.5 parts by mass or more, and is preferably 2 parts by mass or less, more preferably 1 part by mass or less, based on 100 parts by mass of the particulate polymer (X).
[0311] <Other ingredients>
[0312] The composition for the functional layer may contain any other components in addition to the granular polymer (X), the granular polymer (Y), the non-conductive heat-resistant particles and the amine compound. The other components are not particularly limited as long as they do not affect the electrochemical reaction in the electrochemical element, and examples thereof include known additives such as dispersants, viscosity modifiers, and wetting agents. These other components may be used alone or in combination of two or more.
[0313] <Method for preparing composition for electrochemical device functional layer>
[0314] The preparation method of the composition for the functional layer is not particularly limited, and it can be prepared by, for example, mixing the above-mentioned granular polymer (X), granular polymer (Y), water as a dispersion medium, non-conductive heat-resistant particles used as needed, amine compounds and other components. In addition, when the granular polymer (X) and the granular polymer (Y) are prepared by polymerizing the monomer composition in an aqueous solvent, the granular polymer (X) and the granular polymer (Y) can be directly mixed with other components in the form of an aqueous dispersion. In addition, when the granular polymer (X) and the granular polymer (Y) are mixed in the form of an aqueous dispersion, water in the aqueous dispersion can also be used as a dispersion medium.
[0315] Here, the mixing method of the above-mentioned components is not particularly limited. In order to disperse each component efficiently, it is preferred to use a dispersing machine as a mixing device for mixing. Moreover, the dispersing machine is preferably a device that can evenly disperse and mix the above-mentioned components. As the dispersing machine, a ball mill, a sand mill, a pigment dispersing machine, a grinding machine, an ultrasonic dispersing machine, a homogenizer, a planetary mixer, etc. can be cited.
[0316] (Laminate for electrochemical device)
[0317] The electrochemical element laminate of the present invention comprises a substrate and a functional layer formed on the substrate, and the functional layer is formed using the electrochemical element functional layer composition of the present invention. The electrochemical element functional layer composition of the present invention can form a functional layer with excellent adhesion, so if it is a laminate having a functional layer formed using the laminate, the electrochemical properties (e.g., output characteristics and cycle characteristics, etc.) of the electrochemical element having the electrochemical element laminate can be improved.
[0318] <Base material>
[0319] The substrate is not particularly limited. For example, when the functional layer is used as a component constituting a part of the separator, the separator substrate can be used as the substrate. In addition, when the functional layer is used as a component constituting a part of the electrode, an electrode substrate formed by forming an electrode composite material layer on a current collector can be used as the substrate. The usage of the laminate obtained by forming a functional layer on a substrate using a functional layer composition is not particularly limited. For example, the functional layer can be formed on a separator substrate and directly used as an electrochemical element component such as a separator, or the functional layer can be formed on an electrode substrate and directly used as an electrode.
[0320] <<Spacer base material>>
[0321] As the spacer substrate forming the functional layer, there is no particular limitation, and the spacer substrate described in Japanese Patent Publication No. 2012-204303 can be used. Among these, from the aspect of being able to make the overall film thickness of the spacer thinner, thereby being able to increase the ratio of the electrode active material in the electrochemical element and increase the capacity per unit volume, it is preferably a microporous film formed by a resin of a polyolefin system (polyethylene, polypropylene, polybutylene, polyvinyl chloride). In addition, the spacer substrate can also include any layer that can play a desired function in addition to the functional layer in a part thereof.
[0322] <<Electrode base material>>
[0323] As the electrode substrate (positive electrode substrate and negative electrode substrate) forming the functional layer, it is not particularly limited, and the electrode substrate having an electrode composite material layer formed on the current collector can be cited. Here, the components in the current collector and the electrode composite material layer (such as electrode active material (positive electrode active material, negative electrode active material) and electrode composite material layer binding material (positive electrode composite material layer binding material, negative electrode composite material layer binding material) etc.), and the method for forming the electrode composite material layer on the current collector can use known ones, and can use those recorded in, for example, Japanese Patent Publication No. 2013-145763. In addition, the electrode substrate can include any layer having a desired function other than the functional layer in a part thereof.
[0324] <Functional layer>
[0325] The functional layer can be formed on the above-mentioned substrate using the composition for the functional layer of the present invention. Here, the functional layer at least comprises the above-mentioned granular polymer (X), granular polymer (Y), non-conductive heat-resistant particles used as needed, amine compounds and other components. In addition, the components contained in the functional layer are the components contained in the above-mentioned composition for the functional layer, and the preferred existence ratio of these components is the same as the preferred existence ratio of the components in the composition for the functional layer.
[0326] <<Method for forming functional layer>>
[0327] The method for forming a functional layer on a substrate using the composition for a functional layer is not particularly limited, and examples thereof include:
[0328] 1) A method of coating the surface of the substrate with a composition for a functional layer and then drying the composition;
[0329] 2) A method of dipping the substrate in the composition for the functional layer and then drying it;
[0330] 3) A method in which a composition for a functional layer is applied onto a release substrate, dried to form a functional layer, and the obtained functional layer is transferred onto the surface of the substrate.
[0331] In addition, the functional layer may be formed on only one surface of the substrate, or may be formed on both surfaces of the substrate.
[0332] Here, the release substrate is not particularly limited, and a known release substrate can be used.
[0333] Among these, the method 1) is preferred because it is easy to control the thickness of the functional layer. In addition, the method 1) may include, for example, a step of applying the composition for a functional layer on a substrate (coating step) and a step of drying the composition for a functional layer applied on the substrate to form a functional layer (functional layer forming step).
[0334] -Coating process-
[0335] In the coating step, the method for coating the functional layer composition on the substrate is not particularly limited, and examples thereof include a doctor blade method, a reverse roll method, a direct roll method, a gravure method, an extrusion method, and a brush coating method.
[0336] - Functional layer forming process -
[0337] In the functional layer forming step, the method for drying the functional layer composition on the substrate is not particularly limited, and a known method can be used, for example, drying using warm air, hot air, or low-humidity air; vacuum drying; and drying using irradiation of infrared rays, electron beams, etc. The drying conditions are not particularly limited, but the drying temperature is preferably 50° C. or higher and 150° C. or lower, and the drying time is preferably 1 minute or higher and 30 minutes or lower.
[0338] Here, the above-mentioned functional layer composition of the present invention may be a first functional layer composition comprising a granular polymer (X) and a granular polymer (Y) and not containing non-conductive heat-resistant particles, or may be a second functional layer composition comprising non-conductive heat-resistant particles in addition to the granular polymer (X) and the granular polymer (Y).
[0339] Furthermore, when a functional layer is formed on a substrate using the first functional layer composition, an adhesive layer can be obtained as the functional layer.
[0340] Furthermore, by further adding non-conductive heat-resistant particles to the first functional layer composition, which is a binder composition, it is also possible to prepare a second functional layer composition further containing non-conductive heat-resistant particles.
[0341] Furthermore, when a functional layer is formed on a substrate using a second functional layer composition, a single layer (sometimes referred to as a "heat-resistant adhesive layer") can be obtained as a functional layer that simultaneously functions as a heat-resistant layer for improving the heat resistance of the substrate and as an adhesive layer for firmly bonding components to each other.
[0342] As described above, a substrate (laminated body) having a functional layer formed using the second functional layer composition can be produced in shorter steps and time than a conventional substrate having a heat-resistant layer and an adhesive layer, and thus has high productivity.
[0343] Here, the functional layer formed using the second functional layer composition containing non-conductive heat-resistant particles generally has a layer formed of non-conductive heat-resistant particles (hereinafter referred to as "non-conductive heat-resistant particle layer"). Moreover, the non-conductive heat-resistant particle layer is generally configured in a manner that a plurality of non-conductive heat-resistant particles are stacked in the thickness direction of the functional layer.
[0344] The thickness of the non-conductive heat-resistant particle layer is preferably 0.5 μm or more, more preferably 0.8 μm or more, further preferably 1 μm or more, and is preferably 6 μm or less, more preferably 5 μm or less, further preferably 4 μm or less.
[0345] When the thickness of the non-conductive heat-resistant particle layer is not less than the above lower limit, the heat resistance of the functional layer becomes extremely good.
[0346] On the other hand, when the thickness of the non-conductive heat-resistant particle layer is equal to or less than the upper limit, the ion conductivity of the functional layer can be ensured, and the output characteristics of the electrochemical device having the functional layer can be improved.
[0347] In addition, the thickness of the non-conductive heat-resistant particle layer can be adjusted by, for example, changing the coating conditions in the above-mentioned coating step.
[0348] <<Ratio of the volume average particle size of the particulate polymer (X) to the thickness of the non-conductive heat-resistant particle layer>>
[0349] The ratio of the volume average particle size of the granular polymer (X) to the thickness of the above-mentioned non-conductive heat-resistant particle layer (volume average particle size of the granular polymer (X) / thickness of the non-conductive heat-resistant particle layer) is preferably greater than 0.8, more preferably greater than 1.2, further preferably greater than 1.5, further preferably greater than 1.8, preferably less than 10, more preferably less than 6, further preferably less than 4, further preferably less than 3.3.
[0350] If the ratio of the volume average particle size of the granular polymer (X) to the thickness of the non-conductive heat-resistant particle layer is greater than the above lower limit, the granular polymer (X) becomes easier to protrude on the surface of the functional layer in the thickness direction than on the surface of the non-conductive heat-resistant particles, thereby further improving the adhesion of the functional layer.
[0351] On the other hand, when the ratio of the volume average particle size of the particulate polymer (X) to the thickness of the non-conductive heat-resistant particle layer is below the above upper limit, the particulate polymer (X) can be prevented from falling off when the functional layer composition is applied to the substrate, thereby forming a uniform functional layer.
[0352] (Electrochemical Components)
[0353] The electrochemical device of the present invention includes the electrochemical device laminate of the present invention. Such an electrochemical device can exhibit excellent electrochemical characteristics (for example, output characteristics and cycle characteristics).
[0354] Furthermore, the electrochemical device of the present invention is only required to have at least the laminate of the present invention, and therefore may have constituent elements other than the laminate of the present invention unless the effects of the present invention are significantly impaired.
[0355] Furthermore, the electrochemical device of the present invention is not particularly limited, and is, for example, a lithium ion secondary battery or an electric double layer capacitor, and is preferably a lithium ion secondary battery.
[0356] Here, a lithium ion secondary battery as an example of an electrochemical element of the present invention is described below. The lithium ion secondary battery of the present invention has the above-mentioned laminate of the present invention. More specifically, the lithium ion secondary battery has a positive electrode, a negative electrode, a separator with a functional layer formed on a separator substrate (laminate of the present invention) and an electrolyte. The functional layer can be formed only on a single side of the separator substrate, or on both sides of the separator substrate.
[0357] In the following example, the functional layer is formed on the separator substrate, but the functional layer may be formed on the electrode substrate.
[0358] Moreover, in the lithium ion secondary battery of the present invention, the positive electrode and the separator substrate and / or the negative electrode and the separator substrate are firmly bonded in the electrolyte through the functional layer. Therefore, the expansion of the distance between the pole plates of the electrode accompanying repeated charge and discharge is also suppressed, and the battery characteristics such as cycle characteristics become good. In addition, in the case where the functional layer contains non-conductive heat-resistant particles, in the lithium ion secondary battery, the heat resistance of the functional layer separator can be improved. Furthermore, in the case of using a separator having a functional layer containing non-conductive heat-resistant particles, compared with the case of using an existing separator having a heat-resistant layer and an adhesive layer, the time required to manufacture the separator can be shortened and the lithium ion secondary battery can be manufactured with high productivity.
[0359] In addition, as the above-mentioned positive electrode, negative electrode, and electrolyte solution, known positive electrode, negative electrode, and electrolyte solution used in lithium ion secondary batteries can be used.
[0360] <Positive and negative electrodes>
[0361] Specifically, as an electrode (positive electrode and negative electrode), an electrode formed by forming an electrode composite material layer on a current collector can be used. In addition, as a current collector, a current collector formed of metal materials such as iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, platinum, etc. can be used. Among these, as a current collector for a negative electrode, a current collector formed of copper is preferably used. In addition, as a current collector for a positive electrode, a current collector formed of aluminum is preferably used. Furthermore, as an electrode composite material layer, a layer comprising an electrode active material and a binder can be used.
[0362] <Separator with functional layer (laminate)>
[0363] The separator with a functional layer can be produced by, for example, forming the functional layer on the separator substrate using the method for forming the functional layer described above.
[0364] Here, as the separator substrate, there is no particular limitation, and for example, the separator substrate described in Japanese Patent Publication No. 2012-204303 can be used. Among these, from the viewpoint of being able to thin the overall film thickness of the separator with the functional layer, thereby being able to increase the ratio of the electrode active material in the lithium ion secondary battery and increasing the capacity per unit volume, a microporous membrane composed of a polyolefin resin (polyethylene, polypropylene, polybutylene, polyvinyl chloride) is preferred.
[0365] <Electrolyte>
[0366] As the electrolyte, an organic electrolyte in which a supporting electrolyte is dissolved in an organic solvent is generally used. As a supporting electrolyte, for example, a lithium salt can be used in a lithium ion secondary battery. As a lithium salt, for example, LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, (C2F5SO2)NLi, etc. can be cited. Among them, because they are easily soluble in solvents and show a high degree of dissociation, LiPF6, LiClO4, and CF3SO3Li are preferred. In addition, the electrolyte can be used alone or in combination of two or more. Generally, because there is a tendency that the lithium ion conductivity is higher when a supporting electrolyte with a higher degree of dissociation is used, the lithium ion conductivity can be adjusted according to the type of supporting electrolyte.
[0367] As an organic solvent used in the electrolyte, there is no particular limitation as long as it is an organic solvent that can dissolve the supporting electrolyte. For example, in a lithium ion secondary battery, preferably used are: carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), ethyl methyl carbonate (ethyl methyl carbonate (EMC)), and vinylene carbonate; esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as cyclopentane and dimethyl sulfoxide, etc.
[0368] In addition, a mixed solution of these organic solvents may also be used. Among them, carbonates are preferred due to their high dielectric constant and wide stable potential region. Generally, the lower the viscosity of the organic solvent used, the higher the lithium ion conductivity tends to be, so the lithium ion conductivity can be adjusted according to the type of organic solvent.
[0369] In addition, the concentration of the electrolyte in the electrolytic solution can be appropriately adjusted. In addition, a known additive may be added to the electrolytic solution.
[0370] <Method for producing lithium-ion secondary battery>
[0371] The lithium ion secondary battery as the electrochemical element of the present invention can be manufactured by, for example, the following method: the above-mentioned positive electrode and negative electrode are overlapped by a spacer (laminate of the present invention) with a functional layer, and are wound, folded, etc. and placed in a battery container as required, and an electrolyte is injected into the battery container for sealing. Here, porous metal mesh, fuse, PTC element and other overcurrent protection elements, guide plates, etc. can be placed in the battery container as required to prevent the pressure inside the battery from rising and overcharging and discharging. The shape of the battery can be, for example, any one of a coin shape, a button shape, a sheet shape, a cylindrical shape, a square shape, a flat shape, etc.
[0372] Example
[0373] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. In addition, in the following description, "%" and "part" indicating an amount are based on mass unless otherwise specified.
[0374] In a polymer produced by copolymerizing a plurality of monomers, unless otherwise specified, the proportion of a structural unit formed by polymerizing a certain monomer in the polymer is usually consistent with the ratio (charging ratio) of the certain monomer in all monomers used in the polymerization of the polymer.
[0375] In the Examples and Comparative Examples, the volume average particle size, glass transition temperature, electrolyte swelling, thickness of the non-conductive heat-resistant particle layer, ratio of the volume average particle size of the particulate polymer (X) to the thickness of the non-conductive heat-resistant particle layer, and volume ratio of the inorganic particles to the particulate polymer (X) were measured by the following methods. In addition, the air permeability, heat resistance, dry adhesion and wet adhesion of the functional layer, and the output characteristics and cycle characteristics of the secondary battery were measured and evaluated by the following methods.
[0376] <Glass transition temperature>
[0377] The granular polymer (X) and granular polymer (Y) prepared in the examples and comparative examples were used as test samples. 10 mg of the test sample was weighed in an aluminum pan, and the test was performed using a differential thermal analysis measuring apparatus ("EXSTAR DSC6220" manufactured by Seiko Nanotechnologies Corporation) with an empty aluminum pan as a control, in the measurement temperature range of -100°C to 500°C at a heating rate of 10°C / min under the conditions specified in JIS Z 8703 to obtain a differential scanning calorimetry (DSC) curve. In the heating process, the intersection of the baseline immediately before the endothermic peak of the DSC curve where the differential signal (DDSC) becomes 0.05 mW / min / mg or more and the tangent line of the DSC curve at the inflection point that first appears after the endothermic peak was determined as the glass transition temperature (°C).
[0378] <Volume average particle size>
[0379] <<Volume average particle size of granular polymer (X)>>
[0380] The particulate polymer (X) prepared in the examples and comparative examples was used as a measurement sample. 0.1 g equivalent of the measurement sample was weighed and placed in a beaker, and 0.1 mL of an alkylbenzenesulfonic acid aqueous solution (manufactured by Fujifilm Corporation, "DRYWEL") was added as a dispersant. 10 to 30 mL of a diluent (manufactured by Beckman Coulter, Inc., "ISOTON II") was further added to the above beaker, and dispersed for 3 minutes using a 20 W (watt) ultrasonic disperser. Then, a particle size measuring machine (manufactured by Beckman Coulter, Inc., "Multisizer") was used to determine the volume average particle size of the measurement sample under the conditions of pore size: 20 μm, medium: ISOTON II, and number of particles to be measured: 100,000.
[0381] <<Volume average particle size of granular polymer (Y)>>
[0382] The volume average particle size of the granular polymer (Y) prepared in the embodiment is measured by laser diffraction. Specifically, the prepared aqueous dispersion solution containing the binding material (solid content concentration is adjusted to 0.1% by mass) is used as a sample. Then, in the particle size distribution (volume basis) measured using a laser diffraction particle size distribution measuring device (Beckman Coulter Co., Ltd., "LS-230"), the particle size D50 at which the cumulative volume calculated from the small particle size side becomes 50% is used as the volume average particle size.
[0383] <<Volume average particle size of non-conductive heat-resistant particles>>
[0384] In the particle size distribution (volume basis) measured by laser diffraction method, the particle size (D50) at which the cumulative volume calculated from the smaller particle size side is 50% is defined as the volume average particle size of the non-conductive heat-resistant particles.
[0385] <Electrolyte swelling degree>
[0386] The aqueous dispersion containing the granular polymer (X) prepared in the examples and comparative examples was placed in a petri dish made of polytetrafluoroethylene and dried at 25°C for 48 hours to prepare a powder. About 0.2 g of the obtained powder was pressed at 200°C and 5 MPa for 2 minutes to obtain a film. Then, the obtained film was cut into 1 cm squares to obtain test pieces. The mass W0 of the test piece was measured.
[0387] Furthermore, the above-mentioned test piece was immersed in the electrolyte at 60° C. for 72 hours. Then, the test piece was taken out from the electrolyte, the electrolyte on the surface of the test piece was wiped off, and the mass W1 of the test piece after the immersion test was measured.
[0388] Using the measured masses W0 and W1, the electrolyte swelling degree S (times) is calculated by S=W1 / W0.
[0389] In addition, as the electrolyte, a solution in which LiPF6 as a supporting electrolyte was dissolved at a concentration of 1 mol / L in a mixed solvent of ethylene carbonate (EC), diethyl carbonate (DEC) and vinylene carbonate (VC) (volume ratio: EC / DEC / VC=68.5 / 30 / 1.5) was used.
[0390] <Thickness of non-conductive heat-resistant particle layer>
[0391] The cross section of the spacer with the functional layer was observed using a field emission scanning electron microscope (FE-SEM), and the thickness of the non-conductive heat-resistant particle layer was calculated from the obtained SEM image. In addition, the thickness of the non-conductive heat-resistant particle layer was set to the distance from the surface of the spacer substrate coated with the slurry composition to the farthest non-conductive heat-resistant particle in the vertical direction.
[0392] <Ratio of the volume average particle size of the particulate polymer (X) to the thickness of the non-conductive heat-resistant particle layer>
[0393] Based on the volume average particle size of the granular polymer (X) and the thickness of the non-conductive heat-resistant particle layer obtained as described above, the ratio of the volume average particle size of the granular polymer (X) to the thickness of the non-conductive heat-resistant particle layer (volume average particle size of the granular polymer (X) / thickness of the non-conductive heat-resistant particle layer) is calculated.
[0394] <Mixing ratio of inorganic particles and particulate polymer (X)>
[0395] The mixing ratio (volume ratio) of the non-conductive heat-resistant particles (alumina) and the granular polymer (X) was determined based on the feeding amounts of the non-conductive heat-resistant particles (alumina) and the granular polymer (X) when preparing the slurry composition. 3 , the density of magnesium hydroxide is 2.4g / cm 3 The density of the granular polymer (X) is 4.5 g / cm 3 Perform calculations.
[0396] <Air permeability of functional layer>
[0397] For the spacer substrate used in the manufacture of the spacer and the spacer with a functional layer (laminated body), the Gurley value (seconds / 100cc) was measured using a digital Wangyan air permeability / smoothness tester (manufactured by Asahi Seiko Co., Ltd., EYO-5-1M-R). Specifically, based on the Gurley value G0 of the "spacer substrate" and the Gurley value G1 of the manufactured "spacer with a functional layer", the increase in the Gurley value ΔG (= G1-G0) was calculated and evaluated according to the following criteria. The smaller the increase in the Gurley value ΔG, the higher the air permeability of the functional layer and the better the ion conductivity.
[0398] A: The increase in Gurley value is less than 20 seconds / 100cc;
[0399] B: The increase in the Gurley value is 20 seconds / 100cc or more and less than 40 seconds / 100cc;
[0400] C: The increase in the Gurley value is 40 seconds / 100 cc or more.
[0401] <Heat resistance of functional layer>
[0402] The spacers with functional layers prepared in the examples and comparative examples were cut into squares of 12 cm in the TD (width) direction and 12 cm in the MD (length) direction. A line of 10 cm on one side was drawn in the center of the square in a manner that formed a cross in the TD and MD directions to prepare a test piece. Then, the test piece was placed in a constant temperature bath at 150°C for 1 hour. From the lines drawn in TD and MD, {(the length of the line before placement (10 cm) - the length of the positive line after placement) / (the length of the line before placement (10 cm))} × 100 [%] was calculated as the heat shrinkage rate, and the evaluation was performed according to the following criteria. The smaller the heat shrinkage rate, the better the heat resistance of the functional layer.
[0403] A: Thermal shrinkage is less than 3%;
[0404] B: Thermal shrinkage is greater than 3% and less than 5%;
[0405] C: The heat shrinkage is 5% or more.
[0406] <Adhesion before electrolyte immersion (dry adhesion)>
[0407] The negative electrode and the separator with a functional layer (having a functional layer on both sides) prepared in the embodiment and the comparative example were cut into 10 mm wide and 50 mm long, respectively, and the negative electrode and the separator were stacked, and a flat press was used at a temperature of 80 ° C and a load of 1 kN to press for 10 seconds to obtain a test piece. The collector side of the negative electrode of the test piece was faced down, and a transparent tape was pasted on the surface of the electrode. At this time, as a transparent tape, a transparent tape specified in JIS Z1522 was used. In addition, the transparent tape was pre-fixed on a horizontal test bench. Then, one end of the separator was stretched vertically upward at a tensile speed of 50 mm / min, and the stress during peeling was measured. A total of 3 stress measurements were performed. The average value of the total 3 stresses obtained was obtained as the peel strength (N / m), and the adhesion (dry adhesion) between the electrode and the separator separated by the functional layer was evaluated according to the following criteria. The greater the peel strength, the better the dry adhesion.
[0408] A+: Peel strength is 7.0N / m or more;
[0409] A: Peel strength is 5.0 N / m or more and less than 7.0 N / m;
[0410] B: Peel strength is 3.0 N / m or more and less than 5.0 N / m;
[0411] C: Peel strength is 1.0 N / m or more and less than 3.0 N / m;
[0412] D: Peel strength is less than 1.0 N / m.
[0413] <Adhesion after electrolyte immersion (wet adhesion)>
[0414] The positive electrode and the separator with a functional layer (having a functional layer on both sides) prepared in the examples and comparative examples were cut into pieces of 50 mm in length and 10 mm in width, respectively. Then, the cut positive electrode and separator were overlapped to make them stacked. At a temperature of 25°C, a roller press with a load of 10 kN / m was used to press the obtained laminated sheet at a pressing speed of 30 m / min to obtain a test piece. The test piece was immersed in an electrolyte at a temperature of 60°C for 72 hours. Here, as an electrolyte, a solution containing a LiPF6 solution with a concentration of 1M as a supporting electrolyte in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) (volume mixing ratio: EC / DEC=1 / 2) was used. The immersed test piece was taken out of the electrolyte, and the electrolyte on the surface of the test piece was wiped off. The test piece was pressed again under the conditions of 1 MPa, 50°C, and 2 minutes. The face of the current collector side of the positive electrode of the test piece after pressing again is faced downward, and a transparent tape (transparent tape specified in JIS Z 1522) is pasted on the surface of the positive electrode. In addition, the transparent tape is pre-fixed on a horizontal test bench. Then, one end of the spacer is stretched at a tensile speed of 50mm / min vertically above, and the stress during peeling is measured. The measurement is carried out 3 times in total. In addition, the same as above is carried out, and a laminate of a negative electrode and a spacer is obtained separately, and the laminate is pressed to obtain a test piece. Then, the same as the above-mentioned case of using the positive electrode is carried out to obtain a test piece after pressing again, and the stress after electrolyte immersion is measured 3 times in total.
[0415] The average value of the stress obtained by the measurement of the positive electrode and the negative electrode is obtained as the peel strength (N / m), and the adhesion (wet adhesion) between the electrode and the separator through the functional layer after the electrolyte is impregnated is evaluated according to the following criteria. The greater the peel strength, the better the wet adhesion.
[0416] A+: Peel strength is 4.0N / m or more;
[0417] A: Peel strength is 3.0 N / m or more and less than 4.0 N / m;
[0418] B: Peel strength is 2.0 N / m or more and less than 3.0 N / m;
[0419] C: Peel strength is 1.0 N / m or more and less than 2.0 N / m;
[0420] D: Peel strength is less than 1.0 N / m.
[0421] <Output characteristics of secondary batteries>
[0422] The lithium-ion secondary batteries prepared in the examples and comparative examples are charged to 4.3V by constant current constant voltage (CCCV) at a temperature of 25°C to prepare battery cells. The prepared battery cells are discharged to 3.0V by constant current method at 0.2C and 1.5C to obtain the capacity. Then, the discharge capacity retention rate represented by the capacitance ratio (=(1.5C capacity / 0.2C capacity)×100(%)) is obtained. This measurement is performed on 5 battery cells of the lithium-ion secondary battery. Then, the average value of the discharge capacity retention rate of each battery cell is obtained and evaluated according to the following criteria. The larger the value of the discharge capacity retention rate, the better the output characteristics of the secondary battery.
[0423] A: The average value of discharge capacity retention rate is above 90%;
[0424] B: The average value of discharge capacity retention rate is more than 85% and less than 90%;
[0425] C: The average value of the discharge capacity retention rate is less than 85%.
[0426] <Cycle characteristics of secondary batteries>
[0427] After the lithium-ion secondary batteries prepared in the examples and comparative examples were injected with electrolyte, they were left to stand at a temperature of 25°C for 5 hours. Next, they were charged by a constant current method at a temperature of 25°C and 0.2C until the battery cell voltage was 3.65V, and then aged at a temperature of 60°C for 12 hours. Then, they were discharged by a constant current method at a temperature of 25°C and 0.2C until the battery cell voltage was 3.00V. Then, CC-CV charging was performed by a constant current method at 0.2C (the upper limit battery cell voltage was 4.20V), and CC discharge was performed by a constant current method at 0.2C to 3.00V. This 0.2C charge and discharge was repeated 3 times.
[0428] Then, 200 cycles of charge and discharge were performed at a cell voltage of 4.20 to 3.00 V and a charge and discharge rate of 1.0 C at a temperature of 25° C. At this time, the discharge capacity of the first cycle was defined as X1, and the discharge capacity of the 200th cycle was defined as X2.
[0429] Then, the capacity retention rate ΔC'=(X2 / X1)×100(%) was calculated using the discharge capacity X1 and the discharge capacity X2, and the evaluation was performed according to the following criteria. The larger the value of the capacity retention rate ΔC', the better the cycle characteristics of the secondary battery.
[0430] A: Capacity retention rate ΔC´ is above 93%;
[0431] B: Capacity retention rate ΔC´ is greater than 90% and less than 93%;
[0432] C: Capacity retention rate ΔC´ is greater than 87% and less than 90%;
[0433] D: Capacity retention rate ΔC´ is less than 87%.
[0434] (Example 1)
[0435] <Preparation of granular polymer (X1)>
[0436] [Preparation of Monomer Composition (X1)]
[0437] 61.8 parts of styrene as an aromatic monovinyl monomer, 13 parts of 2-ethylhexyl acrylate as an alkyl (meth)acrylate monomer, 25 parts of glycidyl methacrylate as a reactive monomer A, and 0.2 parts of ethylene glycol dimethacrylate as a crosslinking monomer were mixed to prepare a monomer composition (X1).
[0438] [Preparation of Metal Hydroxide]
[0439] To an aqueous solution of 10.0 parts of magnesium chloride dissolved in 200 parts of ion-exchanged water, an aqueous solution of 7.0 parts of sodium hydroxide dissolved in 50 parts of ion-exchanged water was slowly added with stirring to prepare a colloidal dispersion (X1) containing magnesium hydroxide as a metal hydroxide.
[0440] [Suspension polymerization method]
[0441] The granular polymer (X1) as the granular polymer (X) is prepared by suspension polymerization. Specifically, the monomer composition (X1) obtained as described above is added to the colloidal dispersion (X1) containing magnesium hydroxide, and after further stirring, 3.0 parts of tert-butyl peroxy-2-ethylhexanoate (manufactured by NOF Corporation, "PERBUTYL O") as a polymerization initiator are added to obtain a mixed solution. Using a pipeline emulsifying disperser (manufactured by Pacific Machinery Co., Ltd., "Cavitron"), the obtained mixed solution is high-shear stirred at a rotation speed of 12000 rpm for 1 minute to form droplets of the monomer composition (X1) in the colloidal dispersion containing magnesium hydroxide.
[0442] The colloidal dispersion containing magnesium hydroxide in which droplets of the monomer composition (X1) were formed was added to a reactor, heated to 90°C, and a polymerization reaction was carried out for 5 hours. The obtained dispersion was purified by decompression treatment at 90°C for 2 hours using an evaporator to obtain an aqueous dispersion containing a particulate polymer (X1).
[0443] Furthermore, while stirring the aqueous dispersion containing the granular polymer (X1), sulfuric acid was added dropwise at room temperature (25°C) to perform acid washing until the pH reached 6.5 or less. Next, filtration separation was performed, 500 parts of ion exchange water was added to the obtained solid component, and the solid component was slurried again, and the water washing treatment (washing, filtration and dehydration) was repeated 10 times. Then, filtration separation was performed, and the obtained solid component was added to the container of a dryer and dried at 40°C for 48 hours to obtain a dried granular polymer (X1).
[0444] The glass transition temperature and volume average particle size of the obtained particulate polymer (X1) were measured.
[0445] <Preparation of aqueous dispersion containing particulate polymer (Y1)>
[0446] A granular polymer (Y1) was prepared as the granular polymer (Y) in the following manner.
[0447] In a reactor equipped with a stirrer, 70 parts of ion exchange water, 0.15 parts of sodium lauryl sulfate (manufactured by Kao Chemical Co., Ltd., "EMAL (registered trademark) 2F") as an emulsifier, and 0.5 parts of ammonium persulfate as a polymerization initiator were supplied, the gas phase was replaced with nitrogen, and the temperature was raised to 60°C.
[0448] On the other hand, in another container, 50 parts of ion exchange water, 1.0 part of sodium dodecylbenzenesulfonate as a dispersion stabilizer, 90 parts of n-butyl acrylate as an alkyl (meth)acrylate monomer, 5 parts of acrylonitrile as a nitrile group-containing monomer, 4 parts of acrylamide and 0.8 parts of methacrylic acid as reactive monomer B, and 0.2 parts of allyl methacrylate as a crosslinking monomer were mixed to prepare a monomer composition (Y1).
[0449] The obtained monomer composition (Y1) was continuously added to the above-mentioned reactor with a stirrer for 4 hours for polymerization. During the addition, the reaction was carried out at 60°C. After the addition was completed, the reaction was terminated by stirring at 70°C for 3 hours to obtain an aqueous dispersion containing a granular polymer (Y1) as an acrylic polymer. The obtained granular polymer (Y1) had a volume average particle size of 0.15 μm and a glass transition temperature of -40°C.
[0450] <Preparation of composition for functional layer>
[0451] To 100 parts of the granular polymer (X1), 0.2 parts of sodium dodecylbenzenesulfonate (manufactured by Kao Chemical Co., Ltd., “Neopelex G-15”) as an emulsifier, 1.5 parts of carboxymethyl cellulose as a thickener, and 0.5 parts of 1,2-benzo-4-isothiazoline-3-one as an amine compound are added, and then 108 parts of an aqueous dispersion containing the granular polymer (Y1) in terms of solid content are added and mixed to obtain an adhesive composition.
[0452] In 100 parts of aluminum oxide (manufactured by Sumitomo Chemical Co., Ltd., "AKP3000", volume average particle size: 0.7 μm) as non-conductive heat-resistant particles, 0.5 parts of polyacrylic acid as a dispersant are added, ion exchange water is added in a manner that the solid content concentration becomes 55%, and the mixture is mixed using a ball mill, and the obtained mixed solution is added to the binder composition obtained as described above. Further, ion exchange water is added in a manner that the solid content concentration becomes 40% to obtain a slurry composition as a composition for a functional layer. In addition, when the above-mentioned mixed solution is added to the binder composition, the mixing ratio of the non-conductive heat-resistant particles and the granular polymer (X1) in the obtained slurry composition is adjusted to a volume ratio [non-conductive heat-resistant particles: granular polymer (X1)] of 90:10. In addition, the mixing ratio of the non-conductive heat-resistant particles and the granular polymer (X1) in the slurry composition is adjusted to a mass ratio [non-conductive heat-resistant particles: granular polymer (X1)] of 360:10.
[0453] <Production of a separator with a functional layer (laminate)>
[0454] A polyethylene microporous film (thickness: 12 μm) was prepared as a spacer substrate. The slurry composition obtained as described above was applied to the surface of one side of the spacer substrate by a rod coating method. Next, the spacer substrate coated with the slurry composition was dried at 50° C. for 1 minute to form a functional layer. The same operation was performed on the surface of the other side of the spacer substrate to prepare a spacer (laminate) with a functional layer having a functional layer with a thickness of 2.0 μm on both sides of the spacer substrate.
[0455] Furthermore, the air permeability and heat resistance of the functional layer were evaluated using the obtained separator with a functional layer.
[0456] <Production of positive electrode>
[0457] 100 parts of LiCoO2 (volume average particle size: 12 μm) as a positive electrode active material, 2 parts of acetylene black (made by Denka Co., Ltd., "HS-100") as a conductive material, 2 parts of polyvinylidene fluoride (made by Kureha Co., Ltd., "#7208") as a binder for a positive electrode composite material layer, and N-methylpyrrolidone as a solvent were mixed to a total solid content concentration of 70%. They were mixed by a planetary mixer to prepare a positive electrode slurry composition.
[0458] The above-mentioned positive electrode slurry composition is applied to an aluminum foil with a thickness of 20 μm as a current collector using a notch wheel coater so that the film thickness after drying is about 150 μm, and it is dried. The drying is carried out by transporting the aluminum foil in an oven at 60°C for 2 minutes at a speed of 0.5 m / min. Then, it is heated at 120°C for 2 minutes to obtain a positive electrode raw material before pressing. The positive electrode raw material before pressing is rolled with a roller press to obtain a pressed positive electrode having a positive electrode composite material layer (thickness: 60 μm).
[0459] <Production of negative electrode>
[0460] In a 5MPa pressure-resistant container with a stirrer, 33 parts of 1,3-butadiene, 3.5 parts of itaconic acid, 63.5 parts of styrene, 0.4 parts of sodium dodecylbenzene sulfonate as an emulsifier, 150 parts of ion exchange water, and 0.5 parts of potassium persulfate as a polymerization initiator were added, and after sufficient stirring, the polymerization was initiated by heating to 50°C. When the polymerization conversion rate reached 96%, the polymerization was terminated to obtain a mixture containing a binder material (SBR) for the negative electrode composite material layer. A 5% sodium hydroxide aqueous solution was added to the mixture containing the binder material for the negative electrode composite material layer, and after adjusting the pH to 8, the unreacted monomers were removed by heating and reduced pressure distillation. Then, it was cooled to below 30°C to obtain an aqueous dispersion containing the desired binder material for the negative electrode composite material layer.
[0461] 80 parts of artificial graphite (volume average particle size: 15.6 μm) as the negative electrode active material (1) and 16 parts of silicon-based active material SiO as the negative electrode active material (2) were mixed. x(volume average particle size: 4.9 μm), mixed with 2.5 parts of a 2% aqueous solution of sodium carboxymethyl cellulose (manufactured by Nippon Paper Industries, Ltd., "MAC350HC") as a viscosity regulator and ion exchange water, adjusted the solid content concentration to 68%, and further mixed at 25°C for 60 minutes. After adjusting the solid content concentration to 62% with ion exchange water, further mixed at 25°C for 15 minutes to obtain a mixed solution. Add 1.5 parts of the above-mentioned aqueous dispersion containing the binder material for the negative electrode composite material layer and ion exchange water in terms of solid content to the mixed solution, adjust the final solid content concentration to 52%, and further mix for 10 minutes to obtain a mixed solution. The mixed solution is degassed under reduced pressure to obtain a negative electrode slurry composition with good fluidity.
[0462] The above-mentioned negative electrode slurry composition is applied to a copper foil with a thickness of 20 μm as a current collector using a notch wheel coater so that the film thickness after drying is about 150 μm, and it is dried. The drying is carried out by transporting the copper foil in an oven at 60°C for 2 minutes at a speed of 0.5 m / min. Then, it is heated at 120°C for 2 minutes to obtain the negative electrode raw material before pressing. The negative electrode raw material before pressing is rolled using a roller press to obtain a pressed negative electrode having a negative electrode composite material layer (thickness: 80 μm).
[0463] The dry adhesiveness and wet adhesiveness were evaluated using the separator with a functional layer, the positive electrode, and the negative electrode obtained as described above.
[0464] <Manufacturing of lithium-ion secondary batteries>
[0465] The pressed positive electrode produced as described above is cut into a rectangle of 49 cm × 5 cm, and is placed in a manner that the surface on the positive electrode composite material layer side is on the upper side, and the above-mentioned separator with a functional layer cut into 120 cm × 5.5 cm is arranged on the positive electrode composite material layer in a manner that the positive electrode is located on one side of the length direction of the separator with a functional layer. Furthermore, the pressed negative electrode produced as described above is cut into a rectangle of 50 cm × 5.2 cm, and is arranged on the separator with a functional layer in a manner that the surface on the negative electrode composite material layer side is opposite to the separator with a functional layer and the negative electrode is located on the other side of the length direction of the separator with a functional layer. Then, the material obtained is wound using a winding body to obtain a winding body. The wound body was pressed at 70°C and 1MPa to form a flat body, which was then wrapped in an aluminum packaging material outer package as the outer package of the battery, and the electrolyte [solvent: ethylene carbonate / diethyl carbonate / vinyl carbonate (volume ratio) = 68.5 / 30 / 1.5, electrolyte: LiPF6 with a concentration of 1M) was injected in a way that no air was left. Then, the opening of the aluminum packaging material outer package was heat-sealed at a temperature of 150°C to produce a wound lithium-ion secondary battery with a capacity of 800mAh.
[0466] The obtained lithium ion secondary battery was used to evaluate the cycle characteristics and output characteristics of the secondary battery.
[0467] (Example 2)
[0468] The various operations, measurements and evaluations were performed in the same manner as in Example 1 except that the particulate polymer (X2) prepared as follows was used instead of the particulate polymer (X1) when preparing the functional layer composition (slurry composition).
[0469] <Preparation of granular polymer (X2)>
[0470] A granular polymer (X2) was prepared by carrying out the same operation as in the preparation of the granular polymer (X1) in Example 1 except that the monomer composition (X2) was used instead of the monomer composition (X1).
[0471] [Preparation of Monomer Composition (X2)]
[0472] 66.8 parts of styrene as an aromatic monovinyl monomer, 23 parts of 2-ethylhexyl acrylate as an alkyl (meth)acrylate monomer, 10 parts of glycidyl methacrylate as a reactive monomer A, and 0.2 parts of ethylene glycol dimethacrylate as a crosslinking monomer were mixed to prepare a monomer composition (X2).
[0473] (Example 3)
[0474] When preparing the functional layer composition (slurry composition), various operations, measurements and evaluations were performed in the same manner as in Example 1 except that the particulate polymer (X) was replaced with the particulate polymer (X1) by using the particulate polymer (X3) prepared as follows.
[0475] <Preparation of granular polymer (X3)>
[0476] A granular polymer (X3) was prepared by carrying out the same operation as in the preparation of the granular polymer (X1) in Example 1 except that the monomer composition (X3) was used instead of the monomer composition (X1).
[0477] [Preparation of Monomer Composition (X3)]
[0478] 71.8 parts of styrene as an aromatic monovinyl monomer, 26 parts of 2-ethylhexyl acrylate as an alkyl (meth)acrylate monomer, 2 parts of glycidyl methacrylate as a reactive monomer A, and 0.2 parts of ethylene glycol dimethacrylate as a crosslinking monomer were mixed to prepare a monomer composition (X3).
[0479] (Example 4)
[0480] In preparing the functional layer composition (slurry composition), various operations, measurements and evaluations were performed in the same manner as in Example 1 except that the granular polymer (Y2) prepared as follows was used instead of the granular polymer (Y1) as the granular polymer (Y).
[0481] <Preparation of aqueous dispersion containing particulate polymer (Y2)>
[0482] An aqueous dispersion containing the particulate polymer (Y2) was prepared by the same operation as in the preparation of the aqueous dispersion containing the particulate polymer (Y1) in Example 1 except that the monomer composition (Y2) was used instead of the monomer composition (Y1).
[0483] [Preparation of Monomer Composition (Y2)]
[0484] A monomer composition (Y2) was prepared by mixing 50 parts of ion exchange water, 1.0 part of sodium dodecylbenzenesulfonate as a dispersion stabilizer, 94 parts of n-butyl acrylate as an alkyl (meth)acrylate monomer, 1 part of N-isopropylacrylamide and 1 part of methacrylic acid as reactive monomer units B, 2 parts of acrylonitrile as a nitrile group-containing monomer, and 2 parts of allyl methacrylate as a crosslinking monomer.
[0485] (Example 5)
[0486] The various operations, measurements and evaluations were performed in the same manner as in Example 1 except that a particulate polymer (Y3) prepared as follows was used instead of the particulate polymer (Y1) when preparing the slurry composition for a functional layer.
[0487] <Preparation of aqueous dispersion containing particulate polymer (Y3)>
[0488] An aqueous dispersion containing the particulate polymer (Y3) was prepared by the same operation as in the preparation of the aqueous dispersion containing the particulate polymer (Y1) in Example 1 except that the monomer composition (Y3) was used instead of the monomer composition (Y1).
[0489] [Preparation of Monomer Composition (Y3)]
[0490] A monomer composition (Y3) was prepared by mixing 50 parts of ion exchange water, 1.0 part of sodium dodecylbenzene sulfonate as a dispersion stabilizer, 94 parts of n-butyl acrylate as an alkyl (meth)acrylate monomer, 1 part of maleic anhydride and 1 part of methacrylic acid as reactive monomer B, 2 parts of acrylonitrile as a nitrile group-containing monomer, and 2 parts of allyl methacrylate as a crosslinking monomer.
[0491] (Example 6)
[0492] In preparing the functional layer composition (slurry composition), various operations, measurements and evaluations were performed in the same manner as in Example 1 except that the particulate polymer (Y) was replaced with the particulate polymer (Y1) by using the particulate polymer (Y4) prepared as follows.
[0493] <Preparation of aqueous dispersion containing particulate polymer (Y4)>
[0494] An aqueous dispersion containing the particulate polymer (Y4) was prepared by the same operation as in the preparation of the aqueous dispersion containing the particulate polymer (Y1) in Example 1 except that the monomer composition (Y4) was used instead of the monomer composition (Y1).
[0495] [Preparation of Monomer Composition (Y4)]
[0496] A monomer composition (Y4) was prepared by mixing 50 parts of ion exchange water, 1.0 part of sodium dodecylbenzene sulfonate as a dispersion stabilizer, 94 parts of n-butyl acrylate as a (meth)acrylate monomer, 1 part of N-hydroxymethyl acrylamide and 1 part of methacrylic acid as reactive monomer B, 2 parts of acrylonitrile as a nitrile group-containing monomer, and 2 parts of allyl methacrylate as a crosslinking monomer.
[0497] (Example 7)
[0498] The various operations, measurements and evaluations were performed in the same manner as in Example 1 except that the particulate polymer (X4) prepared as follows was used instead of the particulate polymer (X1) when preparing the functional layer composition (slurry composition).
[0499] <Preparation of granular polymer (X4)>
[0500] A granular polymer (X4) was prepared by carrying out the same operation as in the preparation of the granular polymer (X1) in Example 1 except that the monomer composition (X4) was used instead of the monomer composition (X1).
[0501] [Preparation of Monomer Composition (X4)]
[0502] 70.8 parts of styrene as an aromatic monovinyl monomer, 19 parts of 2-ethylhexyl acrylate as an alkyl (meth)acrylate monomer, 10 parts of 4-hydroxybutyl acrylate as a reactive monomer A, and 0.2 parts of ethylene glycol dimethacrylate as a crosslinking monomer were mixed to prepare a monomer composition (X4).
[0503] (Example 8)
[0504] The various operations, measurements and evaluations were performed in the same manner as in Example 1 except that the particulate polymer (X5) prepared as follows was used instead of the particulate polymer (X1) when preparing the functional layer composition (slurry composition).
[0505] <Preparation of granular polymer (X5)>
[0506] A granular polymer (X5) was prepared by the same operation as in the preparation of the granular polymer (X1) of Example 1 except that the colloid dispersion (X5) containing magnesium hydroxide was used instead of the colloid dispersion (X1) containing magnesium hydroxide as the metal hydroxide.
[0507] A colloidal dispersion (X5) containing magnesium hydroxide was prepared by slowly adding an aqueous solution of 8.4 parts of sodium hydroxide dissolved in 50 parts of ion-exchanged water to an aqueous solution of 12.0 parts of magnesium chloride dissolved in 200 parts of ion-exchanged water under stirring.
[0508] (Example 9)
[0509] The various operations, measurements and evaluations were performed in the same manner as in Example 1 except that the particulate polymer (X6) prepared as follows was used instead of the particulate polymer (X1) when preparing the functional layer composition (slurry composition).
[0510] <Preparation of granular polymer (X6)>
[0511] A granular polymer (X6) was prepared by the same operation as in the preparation of the granular polymer (X1) of Example 1 except that the colloid dispersion (X6) containing magnesium hydroxide was used instead of the colloid dispersion (X1) containing magnesium hydroxide as the metal hydroxide.
[0512] A colloidal dispersion (X6) containing magnesium hydroxide was prepared by slowly adding an aqueous solution of 4.2 parts of sodium hydroxide dissolved in 50 parts of ion-exchanged water to an aqueous solution of 6.0 parts of magnesium chloride dissolved in 200 parts of ion-exchanged water under stirring.
[0513] (Example 10)
[0514] The various operations, measurements and evaluations were performed in the same manner as in Example 1 except that the particulate polymer (X7) prepared as follows was used instead of the particulate polymer (X1) when preparing the functional layer composition (slurry composition).
[0515] <Preparation of granular polymer (X7)>
[0516] [Preparation of the first monomer composition (X7)]
[0517] 56.8 parts of styrene as an aromatic monovinyl monomer, 13 parts of 2-ethylhexyl acrylate as a (meth)acrylate monomer, 10 parts of glycidyl methacrylate as a reactive monomer A, and 0.2 parts of ethylene glycol dimethacrylate as a crosslinking monomer were mixed to prepare a first monomer composition (X7).
[0518] [Preparation of Second Monomer Composition (X7)]
[0519] 5 parts of styrene as an aromatic monovinyl monomer and 15 parts of glycidyl methacrylate as a reactive monomer A were mixed to prepare a second monomer composition (X7).
[0520] [Suspension polymerization method]
[0521] The granular polymer (X7) was prepared by suspension polymerization. Specifically, the first monomer composition (X7) obtained as described above was added to the colloidal dispersion (X1) containing magnesium hydroxide prepared in the same manner as in Example 1, and after further stirring, 3.0 parts of tert-butyl peroxy-2-ethylhexanoate (manufactured by NOF Corporation, "PERBUTYL O") as a polymerization initiator was added to obtain a mixed solution. The obtained mixed solution was high-shear stirred at a rotation speed of 12000 rpm for 1 minute using a pipeline emulsifier disperser (manufactured by Pacific Machinery Co., Ltd., "Cavitron") to form droplets of the first monomer composition (X7) in the colloidal dispersion containing magnesium hydroxide.
[0522] A colloidal dispersion containing magnesium hydroxide in which droplets of the first monomer composition (X7) were formed was added to a reactor, heated to 90°C, and subjected to polymerization reaction for 1 hour. After 1 hour, the second monomer composition (X7) was added to the reactor, and polymerization reaction was further carried out at 90°C for 5 hours. The obtained dispersion was purified by decompression treatment at 90°C for 2 hours using an evaporator to obtain an aqueous dispersion containing a particulate polymer (X7).
[0523] (Example 11)
[0524] The same operations, measurements and evaluations as in Example 1 were carried out except that the granular polymer (X8) prepared as follows was used instead of the granular polymer (X1) when preparing the functional layer composition (slurry composition).
[0525] <Preparation of granular polymer (X8)>
[0526] A granular polymer (X8) was prepared in the same manner as in Example 1 except that the monomer composition (X8) was used instead of the monomer composition (X1).
[0527] [Preparation of Monomer Composition (X8)]
[0528] 79.8 parts of cyclohexyl methacrylate as a cycloalkyl (meth)acrylate monomer, 10 parts of 2-ethylhexyl acrylate as an alkyl (meth)acrylate monomer, 10 parts of glycidyl methacrylate as a reactive monomer A, and 0.2 parts of ethylene glycol dimethacrylate as a crosslinking monomer were mixed to prepare a monomer composition (X8).
[0529] (Example 12)
[0530] The same operations, measurements and evaluations as in Example 1 were performed except that the granular polymer (Y5) prepared as follows was used instead of the granular polymer (Y1) when preparing the functional layer composition (slurry composition).
[0531] <Preparation of aqueous dispersion containing particulate polymer (Y5)>
[0532] Except having used the monomer composition (Y5) instead of the monomer composition (Y1), the same operation as in Example 1 was carried out to prepare an aqueous dispersion containing the particulate polymer (Y5).
[0533] [Preparation of Monomer Composition (Y5)]
[0534] A monomer composition (Y5) was prepared by mixing 50 parts of ion exchange water, 1.0 part of sodium dodecylbenzene sulfonate as a dispersion stabilizer, 30 parts of styrene as an aromatic monovinyl monomer, 69 parts of 2-ethylhexyl acrylate as an alkyl (meth)acrylate monomer, 0.5 parts of acrylamide and 0.3 parts of methacrylic acid as reactive monomer B, and 0.2 parts of allyl methacrylate as a crosslinking monomer.
[0535] (Example 13)
[0536] The various operations, measurements and evaluations were performed in the same manner as in Example 1 except that the granular polymer (Y6) prepared as follows was used instead of the granular polymer (Y1) when preparing the functional layer composition (slurry composition).
[0537] <Preparation of aqueous dispersion containing particulate polymer (Y6)>
[0538] In a 5MPa pressure-resistant container with a stirrer, 62 parts of 1,3-butadiene, 35 parts of styrene, 1 part of acrylamide and 2 parts of itaconic acid as reactive monomer B, 0.4 parts of sodium dodecylbenzenesulfonate as an emulsifier, 150 parts of ion exchange water, and 0.5 parts of potassium persulfate as a polymerization initiator were added, and after sufficient stirring, the polymerization was initiated by heating to 50°C. When the polymerization conversion rate reached 96%, the reaction was terminated to obtain a mixture containing a granular polymer (Y6). A 5% sodium hydroxide aqueous solution was added to the mixture, and after adjusting the pH to 8, the unreacted monomers were removed by heating and reduced pressure distillation. Then, the mixture was cooled to below 30°C to obtain an aqueous dispersion containing a granular polymer (Y6).
[0539] (Example 14)
[0540] When preparing the slurry composition, various operations, measurements and evaluations were performed in the same manner as in Example 1, except that as the granular polymer (X), the granular polymer (X9) prepared as follows was used instead of the granular polymer (X1), and the granular polymer (Y7) prepared as follows was used instead of the granular polymer (Y1). The results are shown in Table 3.
[0541] <Preparation of granular polymer (X9)>
[0542] A granular polymer (X9) was prepared by carrying out the same operation as in the preparation of the granular polymer (X1) in Example 1 except that the monomer composition (X9) was used instead of the monomer composition (X1).
[0543] [Preparation of Monomer Composition (X9)]
[0544] 72.8 parts of styrene as an aromatic monovinyl monomer, 24 parts of 2-ethylhexyl acrylate as an alkyl (meth)acrylate monomer, 3 parts of acrylamide as a reactive monomer B, and 0.2 parts of ethylene glycol dimethacrylate as a crosslinking monomer were mixed to prepare a monomer composition (X9).
[0545] <Preparation of aqueous dispersion containing particulate polymer (Y7)>
[0546] A particulate polymer (Y7) was prepared by carrying out the same operation as in the preparation of the aqueous dispersion containing the particulate polymer (Y1) in Example 1 except that the monomer composition (Y7) was used instead of the monomer composition (Y1).
[0547] [Preparation of Monomer Composition (Y7)]
[0548] A monomer composition (Y7) was prepared by mixing 50 parts of ion exchange water, 0.7 parts of sodium dodecylbenzene sulfonate as a dispersion stabilizer, 79 parts of n-butyl acrylate as an alkyl (meth)acrylate monomer, 15 parts of glycidyl methacrylate and 0.8 parts of methacrylic acid as reactive monomer A, 5 parts of acrylonitrile as a nitrile group-containing monomer, and 0.2 parts of allyl methacrylate as a crosslinking monomer.
[0549] (Example 15)
[0550] In preparing the binder composition, the addition amount of the aqueous dispersion containing the particulate polymer (Y1) was changed from 108 parts to 28 parts in terms of solid content, and in preparing the functional layer composition (slurry composition), the addition amount of the mixed solution containing the non-conductive heat-resistant particles was adjusted so that the mixing ratio of the non-conductive heat-resistant particles to the particulate polymer (X1) became 70:30 in terms of volume ratio [non-conductive heat-resistant particles: particulate polymer (X1)] and 280:30 in terms of mass ratio [non-conductive heat-resistant particles: particulate polymer (X1)]. Except for these, various operations, measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 4.
[0551] (Example 16)
[0552] In preparing the binder composition, the addition amount of the aqueous dispersion containing the particulate polymer (Y1) was changed from 108 parts to 12 parts in terms of solid content, and in preparing the functional layer composition (slurry composition), the addition amount of the mixed solution containing the non-conductive heat-resistant particles was adjusted so that the mixing ratio of the non-conductive heat-resistant particles to the particulate polymer (X1) became 50:50 in terms of volume ratio [non-conductive heat-resistant particles: particulate polymer (X1)] and 200:50 in terms of mass ratio [non-conductive heat-resistant particles: particulate polymer (X1)]. Except for these, various operations, measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 4.
[0553] (Example 17)
[0554] When preparing the binder composition, the various operations, measurements and evaluations were performed in the same manner as in Example 1 except that the amount of the aqueous dispersion containing the particulate polymer (Y1) added was changed from 108 parts to 72 parts in terms of solid content.
[0555] (Comparative Example 1)
[0556] The various operations, measurements and evaluations were performed in the same manner as in Example 1 except that the particulate polymer (X10) prepared as follows was used instead of the particulate polymer (X1) when preparing the functional layer composition (slurry composition).
[0557] <Preparation of granular polymer (X10)>
[0558] A granular polymer (X10) was prepared by carrying out the same operation as in the preparation of the granular polymer (X1) in Example 1 except that the monomer composition (X10) was used instead of the monomer composition (X1).
[0559] [Preparation of Monomer Composition (X10)]
[0560] 72.8 parts of styrene as an aromatic monovinyl monomer, 27 parts of 2-ethylhexyl acrylate as an alkyl (meth)acrylate monomer, and 0.2 parts of ethylene glycol dimethacrylate as a crosslinking monomer were mixed to prepare a monomer composition (X10).
[0561] (Comparative Example 2)
[0562] The various operations, measurements and evaluations were performed in the same manner as in Example 1 except that the granular polymer (Y8) prepared as follows was used instead of the granular polymer (Y1) when preparing the functional layer composition (slurry composition).
[0563] <Preparation of aqueous dispersion containing particulate polymer (Y8)>
[0564] A particulate polymer (Y8) was prepared by carrying out the same operation as in the preparation of the aqueous dispersion of the particulate polymer (Y1) in Example 1 except that the monomer composition (Y8) was used instead of the monomer composition (Y1).
[0565] [Preparation of Monomer Composition (Y8)]
[0566] 50 parts of ion exchange water, 1.0 part of sodium dodecylbenzenesulfonate as a dispersion stabilizer, 94.8 parts of n-butyl acrylate as an alkyl (meth)acrylate monomer, 5 parts of acrylonitrile as a nitrile group-containing monomer, and 0.2 parts of allyl methacrylate as a crosslinking monomer were mixed to prepare a monomer composition (Y8).
[0567] [Table 1]
[0568] .
[0569] [Table 2]
[0570] .
[0571] [Table 3]
[0572] .
[0573] [Table 4]
[0574] .
[0575] In addition, in Tables 1 to 4,
[0576] "GMA" means glycidyl methacrylate unit,
[0577] "4HBA" means 4-hydroxybutyl acrylate unit,
[0578] "ST" means styrene unit,
[0579] "2EHA" means 2-ethylhexyl acrylate unit,
[0580] "CHMA" means cyclohexyl methacrylate units,
[0581] "EDMA" means ethylene glycol dimethacrylate units,
[0582] "Aam" means acrylamide unit,
[0583] "NIPAM" means N-isopropylacrylamide unit,
[0584] "MLAH" means maleic anhydride unit,
[0585] "NMA" means N-hydroxymethyl acrylamide unit,
[0586] "MAA" means methacrylic acid unit,
[0587] "IA" represents itaconic acid unit,
[0588] "BA" represents n-butyl acrylate unit,
[0589] "AN" stands for acrylonitrile unit,
[0590] "AMA" means allyl methacrylate units,
[0591] "BD" represents 1,3-butadiene units,
[0592] "BIT" stands for 1,2-benzo-4-isothiazolin-3-one.
[0593] It can be seen from Tables 1 to 4 that the functional layer compositions of Examples 1 to 17, which contain a granular polymer (X) and a granular polymer (Y) having a volume average particle size smaller than the volume average particle size of the granular polymer (X), and one of the granular polymer (X) and the granular polymer (Y) contains a specified reactive monomer unit A and the other contains a specified reactive monomer unit B, can form a functional layer with excellent adhesion.
[0594] It is also found that in the case of the functional layer compositions of Comparative Examples 1 and 2 in which at least one of the particulate polymer (X) and the particulate polymer (Y) does not contain the above-specified reactive monomer unit, the formed functional layer has poor adhesiveness.
[0595] Industrial Applicability
[0596] According to the present invention, a composition for an electrochemical element functional layer capable of forming a functional layer having excellent adhesiveness can be provided.
[0597] Furthermore, according to the present invention, it is possible to provide an electrochemical device laminate having a functional layer formed using the electrochemical device functional layer composition, and an electrochemical device having the electrochemical device laminate.
Claims
1. A composition for an electrochemical element functional layer, comprising a particulate polymer (X) and a particulate polymer (Y), The volume average particle size of the particulate polymer (Y) is smaller than the volume average particle size of the particulate polymer (X), Of the granular polymer (X) and the granular polymer (Y), one contains a reactive monomer unit A, and the other contains a reactive monomer unit B, The reactive monomer unit A is an epoxy-containing monomer unit or a hydroxyl-containing monomer unit, In the case where the reactive monomer unit A is an epoxy-containing monomer unit, the reactive monomer unit B contains at least one selected from a (meth)acrylamide-containing monomer unit, an acid anhydride monomer unit, a sulfonic acid-containing monomer unit, a phosphoric acid-containing monomer unit, and an amino-containing monomer unit, When the reactive monomer unit A is a hydroxyl group-containing monomer unit, the reactive monomer unit B contains at least one selected from a (meth)acrylamide group-containing monomer unit, a carboxylic acid group-containing monomer unit, an acid anhydride monomer unit, a sulfonic acid group-containing monomer unit, a phosphoric acid group-containing monomer unit and an epoxy group-containing monomer unit.
2. The composition for an electrochemical element functional layer according to claim 1, wherein The volume average particle size of the particulate polymer (X) is 1 μm or more and 10 μm or less.
3. The composition for an electrochemical element functional layer according to claim 1, wherein The particulate polymer (X) contains at least one selected from the group consisting of an aromatic monovinyl monomer unit, a cycloalkyl (meth)acrylate monomer unit, and an alkyl (meth)acrylate monomer unit.
4. The composition for an electrochemical element functional layer according to claim 1, wherein The particulate polymer (Y) contains at least one of an aromatic monovinyl monomer unit and an alkyl (meth)acrylate monomer unit.
5. The composition for an electrochemical element functional layer according to claim 1, wherein The content of the particulate polymer (Y) is 10 parts by mass or more and 200 parts by mass or less relative to 100 parts by mass of the particulate polymer (X).
6. The composition for an electrochemical element functional layer according to claim 1, wherein The electrochemical element functional layer composition further includes non-conductive heat-resistant particles.
7. The composition for an electrochemical element functional layer according to claim 6, wherein The content of the particulate polymer (Y) is 0.5 parts by mass or more and 6 parts by mass or less relative to 100 parts by mass of the non-conductive heat-resistant particles.
8. A laminate for an electrochemical element, comprising a substrate and a functional layer for an electrochemical element formed on the substrate, The electrochemical device functional layer is formed using the electrochemical device functional layer composition according to any one of claims 1 to 7.
9. The electrochemical device laminate according to claim 8, wherein: The ratio of the volume average particle size of the particulate polymer (X) to the thickness of the non-conductive heat-resistant particle layer formed of the non-conductive heat-resistant particles is 0.8 or more and 10 or less. 10 . An electrochemical element comprising the laminate for an electrochemical element according to claim 8 .
Citation Information
Patent Citations
Vapor phase epitaxial growth method
JP1991200321A
Electrode for secondary battery, binder for secondary battery electrode, manufacturing method and secondary battery
JP2012204303A
Slurry composition for secondary battery porous film, secondary battery electrode, secondary battery separator, and secondary battery
JP2013145763A
Composition for electrochemical element functional layer, functional layer for electrochemical element, and electrochemical element
WO2020175292A1
Separator including functional layer for electrochemical element, and electrochemical element
WO2020246394A1